Polypropylene-based resin foamed particle and polypropylene-based resin foamed particle molded body
By using polypropylene-based foam particles, its foam layer consists of polypropylene resin and ethylene propylene rubber, and controlling the acetazole insoluble content and melting point range in its n-decane extraction, the problem of high compression stress growth rate when the stress increases is solved, and better impact absorption performance is achieved.
Patent Information
- Application Number
- JP2023147626
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
The existing polypropylene-based foam particle molded products have a high compression stress growth rate when the stress increases, which affects their impact absorption performance.
Polypropylene-based foam particles are used, and the foam layer is composed of a resin containing polypropylene resin and ethylene propylene rubber, which is dispersed in the polypropylene resin, and the acetazole insoluble content in the n-decane extraction of the foam particles is between 0.02 g/g foam particles and 0.10 g/g foam particles, and the melting point is between 140°C and 162°C.
The molding performance and impact absorption performance of polypropylene-based foam particles are improved, the compression stress growth rate when the stress increases is reduced, and better impact performance is obtained.
Smart Images

Figure 2025040685000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to expanded polypropylene resin beads and expanded polypropylene resin bead molded articles. [Background technology]
[0002] Polypropylene resin expanded bead molded articles are lightweight and have excellent compression properties, and therefore are used in various applications, such as shock absorbing materials such as bumper cores, tibia pads, floor spacers, and seat core materials, as well as vehicle components (for example, Patent Document 1). Polypropylene resin expanded bead molded articles are produced, for example, by a method called in-mold molding, in which polypropylene resin expanded beads are filled into a mold and heated with steam. In the in-mold molding method, when steam is supplied into the mold to heat the expanded beads, the expanded beads soften and undergo secondary expansion. This causes the expanded beads in the mold to fuse together, and a molded article having a desired shape corresponding to the shape of the cavity of the mold can be obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-155386 A Summary of the Invention [Problem to be solved by the invention]
[0004] When a polypropylene resin foamed bead molding is used for applications such as vehicle components, it is desirable for the foamed bead molding to have good impact absorbing performance. On the other hand, conventional foamed bead moldings have room for improvement in terms of impact absorbing performance, and there has been a demand for foamed bead moldings that have a low rate of increase in compressive stress with increasing strain when compressive strain is applied.
[0005] The present invention has been made in view of the above background, and aims to provide polypropylene-based resin expanded beads capable of molding an expanded bead molding having good in-mold moldability and a low rate of increase in compressive stress with an increase in compression strain, and a polypropylene-based resin expanded bead molding obtained by molding the expanded beads in a mold. [Means for solving the problem]
[0006] One aspect of the present invention resides in the expanded polypropylene resin particles according to the following items (1) to (4).
[0007] [1] A polypropylene-based resin expanded particle having a foamed layer composed of a polypropylene-based resin composition, the polypropylene-based resin composition constituting the foamed layer contains a polypropylene-based resin and a rubber-like body containing an ethylene propylene-based rubber, the rubber-like material is dispersed in the polypropylene-based resin, an amount of an acetone insoluble matter contained in an n-decane extract of the expanded beads is 0.02 g or more and 0.10 g or less per 1 g of the expanded beads; The melting point Tm of the expanded beads is 140° C. or more and 162° C. or less, The expanded polypropylene resin beads have a difference (Tm-Tc) between the melting point (Tm) of the expanded beads and the crystallization temperature (Tc) of the expanded beads of 38°C or less.
[0008] [2] The expanded polypropylene resin particles according to [1], wherein the average diameter of the rubber-like bodies is 0.1 μm or more and 2 μm or less. [3] The polypropylene-based resin expanded particles according to [1] or [2], wherein the polypropylene-based resin composition constituting the foamed layer contains a polypropylene-based resin derived from recycled polypropylene and an ethylene propylene-based rubber. [4] The expanded polypropylene resin particles according to any one of [1] to [3], wherein the flexural modulus of the polypropylene resin composition constituting the foamed layer is 800 MPa or more and 1,300 MPa or less.
[0009] Another aspect of the present invention is a polypropylene resin foamed bead molding according to the following item [5].
[0010] [5] An expanded polypropylene resin bead molding obtained by molding the expanded polypropylene resin bead according to any one of [1] to [4] in a mold. Effect of the Invention
[0011] According to the above-mentioned aspect, it is possible to provide expanded polypropylene-based resin beads (hereinafter referred to as "expanded beads") capable of molding an expanded bead molding having good in-mold moldability and a low rate of increase in compressive stress with an increase in compression strain, and an expanded polypropylene-based resin bead molding obtained by molding the expanded beads (hereinafter referred to as "molded body") in a mold. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an explanatory diagram showing a method for calculating the heat of fusion of a high-temperature peak. [Diagram 2] FIG. 2 is an electron microscope photograph showing the morphology of recycled polypropylene A1 in the example. [Diagram 3] FIG. 3 is an electron microscope photograph showing the morphology of the expanded beads of Example 4. [Figure 4] FIG. 4 is an electron microscope photograph showing the morphology of the resin particles of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Polypropylene resin foam particles) The polypropylene resin composition constituting the foamed layer of the foamed beads contains at least a polypropylene resin and a rubber-like material containing an ethylene propylene rubber. Details of the polypropylene resin composition will be described later.
[0014] [Acetone insoluble matter in n-decane extract] The acetone insoluble matter contained in the n-decane extract of the expanded beads (hereinafter, the acetone insoluble matter is referred to as "D sol -A insol The amount of D in the expanded beads is 0.02 g or more and 0.10 g or less per 1 g of expanded beads. sol -A insol is mainly composed of ethylene propylene rubber. sol -A insol By setting the amount of D in the above-mentioned specific range, the moldability of the expanded beads in a mold can be improved. In addition, by molding such expanded beads in a mold, a molded article having excellent impact absorption performance can be obtained. The reason for this is that the amount of D in the expanded beads is sol -A insol It is considered that the expanded beads having the amount of in the specific range can reduce the change in stress accompanying the increase in compressive strain, possibly because the excessive increase in stress of the molded body when a high compressive strain is applied is suppressed. Note that the n-decane extract is prepared by heating the expanded beads in n-decane at 145°C and then cooling to 23°C, as described later.
[0015] D in foam particles sol -A insol If the amount of D in the expanded beads is too small, the stress when a high compressive strain is applied to the molded article is likely to be high, which may lead to a decrease in the impact absorption performance. sol -A insol The amount of is preferably 0.03 g or more, and more preferably 0.04 g or more, per 1 g of expanded beads.
[0016] D in foam particles sol -A insol If the amount of D is too large, the moldability of the expanded beads in the mold may be deteriorated. sol -A insolThe amount of D in the expanded beads is preferably 0.09 g or less, more preferably 0.08 g or less, and even more preferably 0.07 g or less per 1 g of the expanded beads. sol -A insol Examples of the method for adjusting the amount of ethylene propylene-based rubber to fall within the above-mentioned specific range include a method for adjusting the amount of ethylene propylene-based rubber contained in the resin raw material or the blending ratio of the resin raw material containing the ethylene propylene-based rubber during the production process of the expanded beads.
[0017] D in foam particles sol -A insol In forming the preferred range of the amount of D sol -A insol The upper and lower limits of the amount of D in the expanded beads can be arbitrarily combined. sol -A insol The preferred range of the amount of may be 0.03 g or more and 0.09 g or less, 0.04 g or more and 0.08 g or less, or 0.04 g or more and 0.07 g or less, per 1 g of expanded beads.
[0018] D in foam particles sol -A insol The method for measuring the amount of is as follows. First, the expanded beads are heated in n-decane at 145°C, and then cooled to 23°C to prepare an n-decane extract. More specifically, the expanded beads are added to n-decane and heated to a temperature of 145°C to dissolve the n-decane-soluble components in the expanded beads in the n-decane. After cooling this n-decane solution to 23°C, the components that are precipitated in the n-decane solution and are insoluble in n-decane at 23°C are removed to obtain an n-decane extract containing n-decane-soluble components. The acetone-insoluble components in the n-decane extract (i.e., the D in the expanded beads) are added to acetone to obtain an n-decane extract containing n-decane-soluble components. sol -A insol Based on the mass of the precipitate obtained above and the mass of the expanded beads used in the measurement, the D contained per 1 g of expanded beads is calculated. sol -A insol The amount of D in the expanded particles can be calculated. sol-A insol A more detailed method for measuring the amount will be described in the Examples.
[0019] [Melting Point] The expanded beads have a melting point Tm of 140° C. or more and 162° C. or less. By setting the melting point Tm of the expanded beads within the above-mentioned specific range, the moldability of the expanded beads in a mold can be improved. In addition, by molding such expanded beads in a mold, a molded product having a low rate of increase in compressive stress when compressive strain is applied and excellent impact absorption performance can be easily obtained.
[0020] If the melting point Tm of the expanded beads is too low, the compression properties of the molded article may be deteriorated. In this case, the change in stress may be large when the compression strain applied to the molded article increases. From the viewpoint of more easily improving the compression properties of the molded article, the melting point Tm of the expanded beads is preferably 143°C or higher, more preferably 145°C or higher, and even more preferably 146°C or higher.
[0021] If the melting point Tm of the expanded beads is too high, it may lead to a decrease in moldability in the mold. From the viewpoint of more easily obtaining expanded beads with good moldability in the mold, the melting point Tm of the expanded beads is preferably 160° C. or lower, and more preferably 158° C. or lower.
[0022] In determining the preferred range of the melting point Tm of the expanded beads, the above-mentioned upper and lower limits of the melting point Tm of the expanded beads can be combined arbitrarily. For example, the preferred range of the melting point Tm of the expanded beads may be 143°C or more and 160°C or less, 145°C or more and 158°C or less, or 146°C or more and 158°C or less.
[0023] The melting point Tm of the expanded beads is determined based on JIS K7121-1987. Specifically, a test piece made of expanded beads is first prepared, and the condition of the test piece is adjusted based on "(2) Measurement of melting temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K7121-1987. The heating rate and cooling rate in the condition adjustment are both 10°C / min. The condition-adjusted test piece is heated from 30°C to 230°C at a heating rate of 10°C / min to obtain a DSC curve, and the apex temperature of the melting peak that appears on the DSC curve is taken as the melting point Tm of the expanded beads. The flow rate of nitrogen gas in the measurement environment is 30 mL per minute. In addition, when multiple melting peaks appear on the DSC curve, the apex temperature of the melting peak with the highest height based on the baseline is taken as the melting point Tm of the expanded beads.
[0024] [The difference between the melting point Tm and the crystallization temperature Tc, Tm-Tc] The difference Tm-Tc between the melting point Tm of the expanded beads and the crystallization temperature Tc of the expanded beads is 38°C or less. Conventionally, when the expanded beads containing ethylene propylene rubber are molded in a mold, the molded body immediately after the molding in the mold is completed tends to shrink locally, and it is difficult to stably obtain a molded body having a desired shape. In contrast, by setting the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc of the expanded beads to be within the specific range, even if the expanded beads contain ethylene propylene rubber, it is possible to easily obtain a molded body having a desired shape by suppressing the local shrinkage of the molded body after molding in the mold.
[0025] If the difference Tm-Tc is too high, the molded product after in-mold molding is likely to shrink locally, and it may be difficult to obtain a good molded product. The lower limit of the difference Tm-Tc in the expanded beads is usually 30°C. The lower limit of the difference Tm-Tc is preferably 32°C.
[0026] The crystallization temperature Tc of the expanded beads is measured using a heat flux differential scanning calorimeter based on JIS K7121-1987. More specifically, the expanded beads are first heated from 23°C to 230°C at a heating rate of 10°C / min. Then, after keeping the temperature at 230°C for 10 minutes, the beads are cooled from 230°C to 30°C at a cooling rate of 10°C / min to obtain a DSC curve. The apex temperature of the crystallization peak in this DSC curve is taken as the crystallization temperature Tc of the expanded beads. The flow rate of nitrogen gas in the measurement environment is 30 mL per minute. When multiple crystallization peaks appear in the DSC curve, the apex temperature of the crystallization peak with the highest peak height is taken as the crystallization temperature Tc of the expanded beads.
[0027] [Polypropylene Resin Composition] The foamed layer of the foamed beads is composed of a polypropylene-based resin composition (hereinafter also referred to as "resin composition") containing a polypropylene-based resin and the rubber-like body. In this specification, the polypropylene-based resin composition refers to a resin composition containing a polypropylene-based resin as a main component. More specifically, the mass ratio of the polypropylene-based resin in the resin composition is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 70 mass% or more, and particularly preferably 80 mass% or more.
[0028] In this specification, the polypropylene-based resin refers to a homopolymer of a propylene monomer (i.e., a propylene homopolymer), a propylene-based copolymer containing 70% by mass or more of a structural unit derived from propylene, and a mixture of a propylene homopolymer and the propylene-based copolymer. The propylene-based copolymer includes a copolymer of propylene and ethylene and / or an α-olefin having 4 or more carbon atoms. The propylene-based copolymer may be a random copolymer or a block copolymer. In addition, the total content of the structural unit derived from ethylene and the structural unit derived from an α-olefin having 4 or more carbon atoms in the propylene-based copolymer is preferably 1% by mass or more and 15% by mass or less, more preferably 2% by mass or more and 12% by mass or less. Note that the polypropylene-based resin and the elastomer such as an ethylene-propylene-based rubber are different substances, and in this respect, the polypropylene-based resin is distinguished from a polypropylene-based resin composition containing an ethylene-propylene-based rubber such as impact polypropylene.
[0029] The rubber-like material contains an ethylene propylene-based rubber. In this specification, the ethylene propylene-based rubber means a rubber-like material composed of an ethylene propylene-based copolymer containing an ethylene component and a propylene component. That is, the ethylene propylene-based rubber may be a copolymer of ethylene and propylene (i.e., EPM). The ethylene propylene-based rubber may also be an ethylene propylene-based copolymer (e.g., EPDM) containing a component derived from a monomer other than ethylene and propylene, such as a diene, within a range that does not impair the above-mentioned action and effect. In the ethylene propylene-based rubber, the mass ratio of the component derived from ethylene to the component derived from propylene (component derived from ethylene:component derived from propylene) is usually 30:70 to 80:20.
[0030] The rubber-like body is dispersed in the polypropylene resin. Specifically, the rubber-like body is preferably present as a domain (i.e., a dispersed phase) dispersed in a matrix (i.e., a continuous phase) made of a polypropylene resin. That is, the foam layer of the foamed beads preferably has a morphology in which the polypropylene resin is the matrix and the rubber-like body is the domain. The rubber-like body may contain a polyethylene resin in addition to the ethylene propylene rubber. The form of the rubber-like body in the foam layer can be confirmed by observing the morphology of the cross section of the foamed beads as shown below.
[0031] The method for observing the morphology of the expanded beads is as follows. First, a sample for observation is cut out from near the center of the expanded bead. Next, the sample for observation is embedded in epoxy resin and subjected to electronic staining with ruthenium tetroxide, and then a slice is prepared from the sample using an ultramicrotome or the like. The slice is placed on the grid of a transmission electron microscope (e.g., "JEM-1040Flash" manufactured by JEOL Ltd.) and observed at a predetermined magnification (e.g., 5000 times), while a cross-sectional photograph of the expanded bead (i.e., a TEM photograph) is taken. From the cross-sectional photograph, the morphology of the polypropylene resin phase and the rubber-like body phase containing the ethylene propylene rubber in the foam layer is visually observed.
[0032] From the viewpoint of stably increasing the moldability of the foamed beads in the mold, the average diameter of the rubber-like body containing the ethylene propylene-based rubber dispersed in the polypropylene-based resin is preferably 0.1 μm or more and 2 μm or less, more preferably 0.3 μm or more and 1.5 μm or less, and even more preferably 0.5 μm or more and 1 μm or less. The average diameter of the rubber-like body is calculated based on the TEM photograph. Specifically, the longest diameter and the shortest diameter of 50 or more domains randomly selected from the domains (i.e., the rubber-like body phase) appearing in the TEM photograph are measured, and then the arithmetic mean of these is calculated. The arithmetic mean value of the longest diameter and the shortest diameter thus obtained is the average diameter of the rubber-like body containing the ethylene propylene-based rubber.
[0033] From the viewpoint of obtaining the above-mentioned effects more easily, from the viewpoint of effective use of resources, and from the viewpoint of material recycling, the polypropylene-based resin composition constituting the foamed layer preferably contains a polypropylene-based resin derived from recycled polypropylene, and more preferably contains a polypropylene-based resin derived from recycled polypropylene and an ethylene propylene-based rubber. That is, the resin composition preferably contains recycled polypropylene containing a polypropylene-based resin, and more preferably contains recycled polypropylene containing a polypropylene-based resin and an ethylene propylene-based rubber.
[0034] Examples of recycled polypropylene include polypropylene resin compositions derived from pre-consumer materials, polypropylene resin compositions derived from post-consumer materials, etc. The recycled polypropylene is preferably recycled polypropylene A (hereinafter referred to as "polypropylene A") derived from post-consumer materials and containing the ethylene propylene rubber.
[0035] In this specification, post-consumer materials refer to "materials discarded from households, or materials generated as products that can no longer be used for their original purposes by commercial facilities, industrial facilities, and various facilities that are end users of products," as described in JIS Q14021:2000. Post-consumer materials also include materials returned from distribution channels.
[0036] More specifically, post-consumer materials include, for example, post-consumer materials derived from automobile parts and post-consumer materials derived from home appliances. Examples of post-consumer materials derived from automobile parts include exterior materials such as bumpers and interior materials such as instrument panels removed from used automobiles, and ASR (i.e., automobile shredding residue) generated during the disposal of automobiles. Polypropylene A containing ethylene propylene-based rubber is recovered from such post-consumer materials. The main component of polypropylene A is preferably impact polypropylene in which a rubber-like body containing ethylene propylene-based rubber is dispersed in a polypropylene-based resin having a melting point of 160°C or higher.
[0037] Moreover, from the viewpoint of effective resource utilization and material recycling, the main component of polypropylene A is preferably a polypropylene-based resin composition a (hereinafter referred to as "resin composition a") derived from an automotive part. More specifically, the mass ratio of the resin composition a derived from an automotive part in polypropylene A is preferably 50 mass% or more, more preferably 60 mass% or more. Moreover, the main component of polypropylene A is more preferably a polypropylene-based resin composition a1 (hereinafter referred to as "resin composition a1") recovered from ASR. More specifically, the mass ratio of the resin composition a1 recovered from ASR in polypropylene A is preferably 50 mass% or more, more preferably 60 mass% or more.
[0038] The resin composition a1 recovered from ASR contains, as a main component, a polypropylene-based resin that has been subjected to a thermal history due to molding processing for forming automotive parts. In addition, the resin composition a1 recovered from ASR usually contains polypropylene-based resins recovered from many automotive parts and many used automobiles. For these reasons, it has been conventionally thought that it is difficult to use the resin composition a1 recovered from ASR for the production of expanded beads. In contrast, the expanded beads have a high D sol -A insolBy setting the amount of , the melting point Tm, and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc within the above-mentioned specific ranges, the moldability of the expanded beads in a mold can be improved even when the resin composition a1 recovered from ASR is used as a raw material. Moreover, by performing molding in a mold using such expanded beads, a molded product having a low rate of increase in compressive stress with an increase in compressive strain can be easily obtained.
[0039] The main component of the polypropylene resin composition a is a polypropylene resin. The mass ratio of the polypropylene resin in the polypropylene resin composition a is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more.
[0040] In this specification, ASR refers to "automobile shredding residue" defined in Article 2-5 of the Law on Recycling of End-of-Life Vehicles, Act No. 87 of 2002. More specifically, ASR refers to the material remaining after dismantling an end-of-life vehicle after removing recyclable parts such as engines and batteries, separating metals and other useful materials from the shredded material, and recovering them. ASR usually contains polypropylene-based resins derived from automobile parts, as well as other plastics and rubbers other than polypropylene-based resins such as polystyrene (PS) and acrylonitrile-butadiene-styrene resin (ABS), various metals, and the like. The method for recovering the resin composition a1 from the ASR is not particularly limited, and the resin composition a1 can be recovered from the ASR by appropriately combining known sorting methods.
[0041] An example of a method for obtaining ASR includes a dismantling process for removing reusable and non-reusable parts from used automobiles, an accessory separation process for removing automobile accessories from the dismantled automobiles that have been through the dismantling process, and a crushing and sorting process for crushing the dismantled automobiles and / or automobile accessories that have been through the separation process, separating metals from the resulting crushed material, and recovering ASR. More specifically, ASR can be obtained by the methods described in Patent Nos. 6609877, 6627142, 6762071, etc.
[0042] For recovery of the resin composition a1, for example, a method of carrying out the following selection steps (α) to (δ) alone or in combination of two or more kinds can be adopted. (α) A magnetic separation process in which metals and non-metals are separated by magnetic force. (β) Wind sorting process to separate light and heavy objects by wind force (γ) A wet gravity separation process in which light and heavy materials are separated using a solvent (δ) Electrostatic sorting process to sort resins based on their ease of charging
[0043] For example, in the wet specific gravity sorting step (γ), the resin composition a1 contained in the ASR can be sorted by a method using water flow classification and sedimentation velocity as described in Japanese Patent No. 3711472, or a method using an apparatus having a pulsating bubbling tank and a sedimentation tank for intermittently discharging air bubbles and a floating matter separation tank for separating substances lighter than water and substances heavier than water as described in Japanese Patent Laid-Open No. 2004-58032. In addition, as described in Japanese Patent Laid-Open No. 2008-178846 and Japanese Patent No. 6762071, these sorting steps can be performed in combination. For example, the wind sorting step and the wet specific gravity sorting step can be combined to separate the light and heavy substances contained in the ASR by wind force, and then the resin composition a1 contained in the ASR can be sorted by immersing each of them separately in a sorting liquid for specific gravity sorting.
[0044] Melting point Tm of polypropylene A Ais preferably 160°C or higher, more preferably 161°C or higher, and even more preferably 162°C or higher. In this case, when compressive strain is applied to the molded article, the compressive stress at a relatively small amount of compressive strain tends to be high. In addition, the change in stress accompanying an increase in compressive strain can be more easily reduced. From the viewpoint of further improving the moldability of the expanded beads in the mold and broadening the range of molding pressures at which a good molded article can be obtained, the melting point Tm of polypropylene A is A It is preferable that the temperature is 168° C. or lower, and more preferably 165° C. or lower.
[0045] Melting point Tm of polypropylene A A The method for measuring the melting point Tm of the expanded beads is the same as the method for measuring the melting point Tm of the expanded beads described above, except that a test piece made of polypropylene A is used instead of the expanded beads.
[0046] Flexural modulus M of polypropylene A A The flexural modulus M of polypropylene A is preferably 800 MPa or more and 1200 MPa or less, more preferably 900 MPa or more and 1100 MPa or less, and even more preferably 950 MPa or more and 1050 MPa or less. In this case, the moldability in the mold of the expanded beads can be more easily improved. A can be calculated based on JIS K7171:2008.
[0047] Melt mass flow rate (MFR) of polypropylene A measured at 230°C and a load of 2.16 kg A is preferably 10 g / 10 min to 40 g / 10 min, more preferably 14 g / 10 min to 35 g / 10 min, and even more preferably 20 g / 10 min to 30 g / 10 min. In this case, while containing a resin component derived from post-consumer materials, the moldability of the expanded beads in the mold can be further improved, and the range of molding pressures under which a good molded product can be obtained can be wider.
[0048] Melt mass flow rate (MFR) of polypropylene A mentioned above Ais a value measured based on JIS K7210-1:2014 under conditions of a test temperature of 230°C and a load of 2.16 kg.
[0049] The ash content of the polypropylene A is preferably 1% by mass or more and 25% by mass or less. In this case, the MFR of the polypropylene A is A Even when the pressure is relatively high, the moldability of the expanded beads in the mold can be improved, and the range of molding pressure within which a good molded article can be obtained can be broadened.
[0050] By using polypropylene A having an ash content within the above-mentioned specific range, the bubble diameter of the expanded beads can be made relatively small and the bubble membrane can be made thin. In addition, it is considered that such expanded beads are easily softened by heating, while the resin is not easily stretched. Therefore, it is considered that by using polypropylene A having an ash content within the above-mentioned specific range, the shrinkage of the molded body can be easily suppressed even when molding is performed in a mold at a high molding pressure.
[0051] The ash content of the polypropylene A is more preferably 2% by mass or more, and further preferably 3% by mass or more. In this case, a polypropylene-based resin composition having a relatively high ash content, such as the resin composition a1 derived from ASR, can be more easily blended, and the resin component derived from post-consumer materials can be more effectively utilized.
[0052] From the viewpoint of further improving the moldability of the expanded beads in the mold, the ash content of the polypropylene A is more preferably 20% by mass or less, even more preferably 15% by mass or less, still more preferably 10% by mass or less, particularly preferably 8% by mass or less, and most preferably 6% by mass or less.
[0053] The above-mentioned upper limit and lower limit of the ash content can be arbitrarily combined to define a preferred range of the ash content of polypropylene A. For example, the preferred range of the ash content of polypropylene A may be 1% by mass or more and 20% by mass or less, 2% by mass or more and 15% by mass or less, 2% by mass or more and 10% by mass or less, 3% by mass or more and 8% by mass or less, or 3% by mass or more and 6% by mass or less.
[0054] The ash content of the polypropylene A can be measured in accordance with the direct incineration method (Method A) of JIS K7250-1:2006. More specifically, the ash content of the polypropylene A can be calculated from the mass of the residue remaining after the polypropylene A is combusted. The ash content contained in the combustion residue of the polypropylene A is mainly a component derived from inorganic substances contained in the polypropylene A, such as inorganic fillers.
[0055] The polypropylene A preferably exhibits a morphology in which the polypropylene resin is the matrix (i.e., the continuous phase) and the rubber-like body containing the ethylene propylene rubber is the domain (i.e., the dispersed phase). In this case, expanded beads having good moldability in a mold can be obtained more stably. In addition, by performing molding in a mold using the expanded beads, a molded body having good mechanical properties such as compressive strength can be obtained more easily. From the same viewpoint, it is more preferable that the melting point of the polypropylene resin constituting the matrix in the polypropylene A is 160°C or higher. The domain of the rubber-like body in the polypropylene A may contain a polyethylene resin in addition to the ethylene propylene rubber.
[0056] The method for observing the morphology of the polypropylene A is as follows. First, a sample for observation is cut out from the polypropylene A. There is no particular limitation on the method for cutting out the sample for observation. For example, when the shape of the polypropylene A is a cylindrical pellet, the pellet may be cut perpendicularly to the height direction of the pellet so as to pass through the center of the pellet. In this way, a sample for observation in which the cross section of the center of the pellet made of the polypropylene A is exposed can be obtained. Next, the sample for observation is embedded in an epoxy resin and subjected to electronic staining with ruthenium tetroxide, and then a slice is prepared from the sample using an ultramicrotome or the like. The slice is placed on the grid of a transmission electron microscope (for example, "JEM-1040Flash" manufactured by JEOL Ltd.) and observed at a predetermined magnification (for example, 5000 times), and a cross-sectional photograph of the polypropylene A (i.e., a TEM photograph) is taken. From the cross-sectional photograph, the morphology of the polypropylene resin phase and the rubber-like body phase containing the ethylene propylene rubber in the polypropylene A is visually observed.
[0057] From the viewpoint of stably increasing the moldability of the foamed beads in the mold, the average diameter of the rubber-like body containing the ethylene propylene-based rubber in the polypropylene A is preferably 0.5 μm or more and 5 μm or less, more preferably 0.8 μm or more and 3 μm or less, and even more preferably 1 μm or more and 2 μm or less. The average diameter of the rubber-like body in the polypropylene A is calculated based on the TEM photograph. Specifically, the longest diameter and the shortest diameter of 50 or more domains randomly selected from the domains (i.e., the rubber-like body phase) appearing in the TEM photograph are measured, and then the arithmetic mean of these is calculated. The arithmetic mean value of the longest diameter and the shortest diameter thus obtained is the average diameter of the rubber-like body containing the ethylene propylene-based rubber.
[0058] The acetone insoluble matter in the n-decane extract of polypropylene A (i.e., D sol -A insolThe amount of D in polypropylene A is more preferably 0.05 g to 0.30 g, even more preferably 0.06 g to 0.25 g, and particularly preferably 0.08 g to 0.20 g. In this case, the expanded beads can be obtained more easily. sol -A insol is a component derived mainly from ethylene propylene rubber. D in polypropylene A sol -A insol The amount of D per 1 g of polypropylene A was measured using polypropylene A instead of the expanded particles. sol -A insol Except for calculating the amount of D sol -A insol The method for measuring the amount of is similar to that of
[0059] The polypropylene A may contain resins other than polypropylene-based resins and elastomers other than ethylene propylene-based rubbers, etc., within the scope that does not impair the above-mentioned action and effect. Examples of resins that can be contained in the polypropylene A include polystyrene-based resins, polyethylene-based resins, and acrylonitrile-butadiene-styrene resins, and examples of elastomers include ethylene butene rubber and ethylene octene rubber. These resins and elastomers may be derived from post-consumer materials.
[0060] The polypropylene A may contain inorganic substances such as talc, silica, and glass fiber within a range that does not impair the above-mentioned action and effect. The main component of the inorganic substances contained in the polypropylene A is preferably talc. In this case, even when polypropylene A having a relatively high melting point is used, the fusibility of the expanded beads can be further improved. As a result, the moldability of the expanded beads in the mold can be further improved. The reason for this is thought to be that the average bubble diameter of the expanded beads is likely to become small.
[0061] The polypropylene A may contain additives such as a cell regulator, a crystal nucleating agent, a flame retardant, a flame retardant assistant, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet absorber, a light stabilizer, an antibacterial agent, and a colorant, within a range that does not impair the above-mentioned action and effect. In addition, the polypropylene A preferably contains carbon black as a colorant. In this case, for example, the content of carbon black in the polypropylene A may be 0.1% by mass or more and 2% by mass or less, or 0.2% by mass or more and 1% by mass or less. By setting the content of carbon black in the polypropylene A within the above-mentioned specific range, a molded product having excellent designability and a mottled pattern of relatively light black (gray) and white can be obtained.
[0062] From the viewpoint of more reliably obtaining the above-mentioned action and effect, it is preferable that the foam layer of the foamed beads is composed of a molten mixture of the recycled polypropylene A and polypropylene-based resin B (hereinafter referred to as "resin B"). That is, it is preferable that the resin composition constituting the foam layer is a molten mixture of polypropylene A and resin B.
[0063] Resin B used in the expanded beads may be a polypropylene-based resin that has not been subjected to a thermal history due to molding or the like for forming a molded product (i.e., a non-recycled polypropylene-based resin), or may be a polypropylene-based resin that has been subjected to a thermal history (more specifically, a recycled polypropylene-based resin that has been material recycled). From the viewpoint of being able to more stably improve the moldability in the mold of the expanded beads, it is preferable that resin B is a non-recycled polypropylene-based resin.
[0064] Melting point Tm of resin B B is preferably 130° C. or higher and lower than 160° C., more preferably 135° C. or higher and 158° C. or lower, further preferably 140° C. or higher and 156° C. or lower, and particularly preferably 142° C. or higher and 155° C. or lower. In this case, the expandability during the production process of the expanded beads can be further improved, and the moldability of the expanded beads in the mold can be further improved.
[0065] Melting point Tm of resin B B The method for measuring the melting point Tm of the expanded beads is the same as the method for measuring the melting point Tm of the expanded beads described above, except that a test piece made of resin B is used instead of the expanded beads. When two or more types of polypropylene resins are used as resin B in the production of the expanded beads, the multiple types of polypropylene resins are melt-mixed in the same ratio as in the production process of the expanded beads, and a test piece made of a molten mixture of these polypropylene resins is used.
[0066] Flexural modulus M of resin B B The flexural modulus M of resin B is preferably 800 MPa or more and 1400 MPa or less, more preferably 850 MPa or more and 1350 MPa or less, and even more preferably 900 MPa or more and 1300 MPa or less. B In the case where two or more kinds of polypropylene resins are used as resin B in the production of expanded beads, the polypropylene resins are melt-mixed in the same ratio as in the production process of expanded beads, and the flexural modulus of a test piece made of a molten mixture of these polypropylene resins is calculated as the flexural modulus M of resin B. B Let us assume that.
[0067] The ash content of resin B is preferably less than 1 mass %, more preferably 0.5 mass % or less, in which case good expandability can be maintained during the production process of the expanded beads while improving moldability in the mold, and the range of molding pressures within which good molded articles can be obtained can be broadened.
[0068] The ash content of B described above can be measured in accordance with the direct incineration method (Method A) of JIS K7250-1: 2006. More specifically, the ash content of resin B can be calculated from the mass of the residue remaining after burning resin B.
[0069] Melt mass flow rate (MFR) of resin B measured at 230°C and a load of 2.16 kg BThe melt mass flow rate MFR of resin B is preferably 6 g / 10 min or more and 9 g / 10 min or less. In this case, the moldability in the mold of the expanded beads can be more stably improved. When two or more kinds of polypropylene resins are used as resin B, the melt mass flow rate of a sample obtained by melt-mixing these polypropylene resins in the same ratio as the compounding ratio in the manufacturing process of the expanded beads is defined as the melt mass flow rate MFR of resin B. B Let us assume that.
[0070] Heat of fusion of resin B H B The heat of fusion H of the polypropylene resin B is preferably 50 J / g or more and 100 J / g or less. In this case, the moldability of the expanded beads in the mold can be more stably improved. From the same viewpoint, the heat of fusion H of the polypropylene resin B is preferably 50 J / g or more and 100 J / g or less. B It is more preferable that the heat of fusion is 60 J / g or more and 98 J / g or less, and further preferably 65 J / g or more and 96 J / g or less. When two or more kinds of polypropylene resins are used as resin B, the heat of fusion of a sample obtained by melt-mixing these polypropylene resins in the same mass ratio as that in producing the resin particles is defined as the heat of fusion H of resin B. B Let us assume that.
[0071] The heat of fusion of resin B can be determined based on a DSC curve obtained by performing differential scanning calorimetry (DSC) in accordance with JIS K 7122-1987. Specifically, resin B is used as a test piece, and the condition of the test piece is adjusted based on "(2) Measurement of melting temperature after a certain heat treatment" in "3. Conditioning of test piece" in JIS K 7122-1987. The heating rate and cooling rate in the condition adjustment are both 10°C / min, and the temperature range is from 23°C to 230°C. After that, the condition-adjusted test piece is heated again from 23°C to 230°C at a rate of 10°C / min to obtain a DSC curve (DSC curve at the time of the second heating). The flow rate of nitrogen gas in the measurement environment is 30 mL per minute. In this DSC curve, a straight line is drawn connecting the point corresponding to 80°C and the high-temperature end point of the melting peak with the highest apex temperature. The heat of fusion of resin B, H Bcan be calculated based on the area of the region enclosed by the straight line thus determined and the melting peak of the DSC curve.
[0072] Resin B is preferably a propylene-based copolymer containing 70% by mass or more of structural units derived from propylene, and more preferably a propylene-based copolymer containing 80% by mass or more of structural units derived from propylene. By using such resin B, the expanded beads can be more easily obtained. Resin B may contain two or more kinds of propylene-based copolymers.
[0073] From the same viewpoint, resin B is preferably a copolymer of propylene and ethylene and / or an α-olefin having 4 or more carbon atoms. Moreover, the copolymer is more preferably a random copolymer (i.e., a propylene-based random copolymer).
[0074] Examples of the α-olefin used in the propylene-based copolymer include 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-butene, etc. In the propylene-based copolymer, the total content of the structural units derived from ethylene and the structural units derived from the α-olefins having 4 or more carbon atoms (i.e., the content of the comonomer components) is preferably 1% by mass or more and 15% by mass or less, more preferably 2% by mass or more and 12% by mass or less.
[0075] When two or more polypropylene resins are used as resin B, the content of the comonomer component is defined as the ratio of the mass of the comonomer component to the total mass of these polypropylene resins (i.e., the total mass of resin B). In other words, when two or more polypropylene resins are used as resin B, the content of the comonomer component is the sum of the content of the ethylene-derived structural unit and the content of the α-olefin having 4 or more carbon atoms in a sample obtained by melt-mixing multiple polypropylene resins in the same ratio as the blending ratio in the manufacturing process of the expanded beads.
[0076] The main component of the resin B is preferably a propylene-based copolymer b1 containing a structural unit derived from ethylene (i.e., an ethylene component) as a copolymerization component and / or a propylene-based copolymer b2 containing a structural unit derived from ethylene and 1-butene (i.e., an ethylene component and a butene component) as a copolymerization component. Such a propylene-based copolymer b1 (hereinafter referred to as "copolymer b1") may be a propylene-ethylene random copolymer. Also, an example of the propylene-based copolymer b2 (hereinafter referred to as "copolymer b2") may be a propylene-ethylene-butene random copolymer. The sum of the proportion of copolymer b1 and the proportion of copolymer b2 with respect to the total mass of the resin B contained in the expanded beads is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0077] When resin B contains copolymer b1 as a main component, the content of the ethylene component in copolymer b1 is preferably 1% by mass or more, more preferably 2% by mass or more, which can further improve the moldability of the expanded beads in the mold when molding is performed at a low molding pressure.
[0078] The content of the ethylene component in the copolymer b1 is preferably 6% by mass or less, more preferably 5% by mass or less, further preferably 4% by mass or less, and particularly preferably 3% by mass or less, in which case a molded product having good compressive strength and the like can be more easily obtained.
[0079] When resin B contains copolymer b2 as a main component, the total content of the ethylene component and the butene component in copolymer b2 is preferably 2% by mass or more, more preferably 4% by mass or more, and even more preferably 6% by mass or more, in which case the moldability of the expanded beads in the mold can be further improved when the molding is performed in the mold at a low molding pressure.
[0080] The total content of the ethylene component and the butene component in the copolymer b2 is preferably 15% by mass or less, more preferably 12% by mass or less, in which case a molded product having good compressive strength and the like can be more easily obtained.
[0081] In addition, from the viewpoint of enabling molding at a relatively low molding pressure and making it easier to obtain a molded product having good compressive strength, etc., the ratio of the butene component content to the ethylene component content in copolymer b2 is preferably 7 or more and 25 or less, more preferably 8 or more and 20 or less, and even more preferably 10 or more and 18 or less.
[0082] The contents of the ethylene-derived component and the butene-derived component in the resin B can be determined, for example, based on an IR spectrum. The method for measuring the contents of the ethylene-derived component and the butene-derived component in the resin B will be described in detail in the examples.
[0083] In configuring a preferred range for the content of the comonomer component in Resin B, the above-mentioned upper limit value and lower limit value can be combined arbitrarily.
[0084] The resin B may contain additives such as a bubble adjuster, a crystal nucleating agent, a flame retardant, a flame retardant assistant, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet absorber, a light stabilizer, an antibacterial agent, and a colorant, as long as the above-mentioned action and effect are not impaired.
[0085] In order to obtain the above-mentioned effects more reliably, the resin composition constituting the foamed layer of the foamed beads has a melting point Tm A The recycled polypropylene A has a melting point Tm B It is more preferable that the temperature of the polypropylene resin B is 130° C. or more and less than 160° C. The expanded beads having a foam layer made of such a molten mixture have excellent moldability in a mold. In addition, by molding such expanded beads in a mold, a molded product with a small change in stress due to an increase in compression strain can be more stably obtained.
[0086] The blending ratio of polypropylene A to resin B in the resin composition constituting the foamed layer (where the sum of the mass of polypropylene A and the mass of resin B is taken as 100 mass%) is preferably polypropylene A:resin B=3:97 to 70:30. That is, the mass ratio of polypropylene A to the sum of polypropylene A and resin B blended in the resin composition is preferably 3 mass% or more and 70 mass% or less.
[0087] By making the mass ratio of polypropylene A 3% by mass or more, it becomes easier to increase the compressive stress at a relatively small amount of compressive strain when compressive strain is applied to the molded body. In this case, the rate of increase in compressive stress with increasing strain can be further reduced, and the impact absorption performance of the molded body can be further improved. In this case, the amount of polypropylene A derived from post-consumer materials that can be blended in the resin particles can be increased, and the resin components derived from post-consumer materials can be more effectively utilized.
[0088] From the viewpoint of further improving the impact absorption performance of the molded body, the mass ratio of polypropylene A to the total of polypropylene A and resin B is preferably 5 mass% or more, more preferably 8 mass% or more, and even more preferably 10 mass% or more.
[0089] Furthermore, by setting the mass ratio of polypropylene A to 70 mass% or less, the moldability of the expanded beads in the mold can be improved more easily. From the viewpoint of more stably increasing the moldability of the expanded beads in the mold, the mass ratio of polypropylene A to the total of polypropylene A and resin B is preferably 65 mass% or less, more preferably 60 mass% or less, and even more preferably 50 mass% or less.
[0090] In configuring a preferred range of the mass ratio of polypropylene A, it is possible to arbitrarily combine the above-mentioned upper limit value and lower limit value of the mass ratio of polypropylene A. For example, a preferred range of the mass ratio of polypropylene A to resin B may be polypropylene A:resin B = 3:97 to 65:35, 8:92 to 60:40, or 10:90 to 50:50.
[0091] Melting point Tm of polypropylene A A and the melting point Tm of resin B B Difference from Tm A -Tm B The temperature is preferably from 5° C. to 30° C., more preferably from 8° C. to 28° C., and even more preferably from 10° C. to 25° C. In this case, while containing a resin component derived from post-consumer materials, the moldability of the expanded beads in the mold can be further improved, and the range of molding pressures under which a good molded product can be obtained can be broadened.
[0092] Melt mass flow rate (MFR) of polypropylene A A and Melt Mass Flow Rate MFR of Resin B B Difference between MFR A -MFR B is preferably 5 g / 10 min to 35 g / 10 min, more preferably 8 g / 10 min to 30 g / 10 min, and even more preferably 12 g / 10 min to 25 g / 10 min. In this case, the variation in moldability of the expanded beads in the mold can be further reduced.
[0093] Flexural modulus M of polypropylene A A Flexural modulus M of resin B B Ratio of M B / M A The flexural modulus M of the resin B to be combined with the polypropylene A is preferably 0.8 or more and 2 or less, more preferably 0.9 or more and 1.6 or less, and even more preferably 1 or more and 1.5 or less. BWithin the above-mentioned specific range, the in-mold moldability of the expanded beads can be improved while the resin component derived from the post-consumer material is contained. Furthermore, by performing in-mold molding using such expanded beads, the compressive strength of the molded body can be more easily increased.
[0094] By using polypropylene A having a melting point of a specific temperature or higher, it becomes easier to increase the compressive stress at a relatively small amount of compressive strain of the obtained molded body. On the other hand, recycled polypropylene A has a melting point Tm A Flexural modulus M A The ratio of polypropylene A to polypropylene B tends to be relatively low, and the moldability of the foamed beads in the mold tends to be reduced. A Lower melting point Tm B On the other hand, by including Resin B which has a relatively high flexural modulus, the balance between the melting point and flexural modulus in the resin composition is improved, making it easier to consistently obtain expanded beads which can be used to mold into molded articles which have excellent in-mold moldability and compressive strength.
[0095] The heat of fusion of the polypropylene A, H A is 60 J / g or more and 100 J / g or less, and the heat of fusion H B is 60 J / g or more and 100 J / g or less, and the heat of fusion H A and the heat of fusion H B Tonowa H A +H B The heat of fusion of polypropylene A is preferably 140 J / g or more and 175 J / g or less. When comparing the physical properties of polypropylene A derived from post-consumer materials between different lots, the physical properties tend to vary widely. In contrast, the heat of fusion of polypropylene A, H A and the heat of fusion of resin B, H B and are within the above-mentioned specific ranges, and further, the sum of the heats of fusion H A +H BBy setting the heat of fusion H of polypropylene A within the above-mentioned specific range, even when polypropylene A having large variations in physical properties is used, the moldability of the expanded beads in the mold can be improved more stably. A Heat of fusion of resin B against B The ratio of H B / H A is preferably 0.7 or more and 1.2 or less, and more preferably 0.8 or more and 1.1 or less.
[0096] The heat of fusion of polypropylene A, H A The measurement method is the same as the above-mentioned measurement of the heat of fusion H of resin B, except that polypropylene A is used as the test piece instead of resin B. B The measurement method is the same as that of
[0097] [Fusing layer] The expanded beads may have a single-layer structure consisting of only a foamed layer made of the resin composition, or may have a multi-layer structure including a foamed layer made of the polypropylene resin composition and a fusion layer that is provided to enhance the fusion between the expanded beads during in-mold molding and covers the foamed core layer. The fusion layer may be present on the entire surface of the expanded beads, or may be present on a part of the surface. The fusion layer may be in a foamed state or a non-foamed state, but is preferably in a substantially non-foamed state. The above-mentioned "non-foamed state" includes a state in which the fusion layer is not foamed and does not contain bubbles, and a state in which the bubbles disappear after foaming, and means that there is almost no bubble structure in the fusion layer. In addition, when the expanded beads have a foamed layer and a fusion layer, the foamed layer covered by the fusion layer may be called the "foamed core layer".
[0098] The method for producing expanded beads having a fusion layer is not particularly limited, and examples thereof include a method of foaming resin beads having a non-foamed core layer and a fusion layer covering the core layer, a method of foaming a non-foamed core layer to obtain an expanded core layer, and then attaching a fusion layer to the surface of the expanded core layer, etc. When foaming resin beads having a fusion layer on the surface to obtain expanded beads, it is preferable to adopt a method in which, when producing resin beads, a molten mixture for forming the core layer and a resin melt for forming the fusion layer are co-extruded using an extrusion device capable of co-extrusion, thereby laminating the fusion layer on the surface of the core layer.
[0099] The proportion of the fusion layer in the expanded beads is preferably about 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 10% by mass or less.
[0100] Examples of the base resin constituting the fusion layer include a crystalline polyolefin resin having a melting point lower than that of the resin composition constituting the foamed core layer, and an amorphous polyolefin resin having a softening point lower than that of the resin composition constituting the foamed core layer. The base resin constituting the fusion layer is preferably a polypropylene resin and / or a polyethylene resin, and more preferably a polypropylene resin.
[0101] When the adhesive layer is made of a crystalline polyolefin resin having a melting point, the melting point of the crystalline polyolefin resin is preferably 100°C or more and less than 160°C, more preferably 110°C or more and 158°C or less, and even more preferably 120°C or more and 155°C or less.
[0102] In addition, the difference between the melting point of the resin composition constituting the foamed core layer and the melting point of the resin composition constituting the fusion layer is preferably about 1° C. to 40° C., more preferably 2° C. to 35° C., and even more preferably 5° C. to 30° C. In this case, the moldability of the foamed beads in the mold can be improved even when the molding pressure is relatively low. In addition, by molding such foamed beads in the mold, a molded product having good compression properties can be more easily obtained.
[0103] The expanded beads may have a cylindrical shape with a through hole passing through the inside in the axial direction. For example, the expanded beads may have a bottom surface, a top surface disposed above the bottom surface and having a shape substantially the same as that of the bottom surface, and a side peripheral surface connecting the edge of the bottom surface and the edge of the top surface, and may have a through hole passing through the inside of the expanded beads in the axial direction and opening at the bottom surface and the top surface. The cylindrical shape includes a cylinder and a square tube. The number of through holes may be two or more.
[0104] The average diameter of the through holes is preferably less than 1 mm, more preferably 0.95 mm or less, even more preferably 0.90 mm or less, and particularly preferably 0.85 mm or less. In this case, it is possible to easily shorten the cooling time during in-mold molding while ensuring the compression properties of the molded body. Furthermore, by using such expanded beads, a molded body with good surface properties can be easily obtained even if the curing process of the expanded beads is shortened or omitted. From the viewpoint of ease of production, the average diameter of the expanded beads is preferably about 0.2 mm or more, and more preferably 0.3 mm or more.
[0105] In addition, the ratio of the average pore size of the through holes to the average outer diameter of the expanded beads is preferably 0.4 or less, more preferably 0.3 or less, and even more preferably 0.25 or less. In this case, it is possible to easily shorten the cooling time during in-mold molding while ensuring the compression properties of the molded body. Furthermore, by using such expanded beads, a molded body with good surface properties can be easily obtained even if the curing process of the expanded beads is shortened or omitted. From the viewpoint of ease of production, it is preferable that the ratio of the average pore size of the through holes to the average outer diameter of the expanded beads is 0.1 or more.
[0106] [Flexural modulus] The flexural modulus of the resin composition constituting the foam layer of the foamed beads is preferably 800 MPa or more and 1300 MPa or less. In this case, the moldability of the foamed beads in a mold can be more easily improved. In addition, by producing a molded article using such foamed beads, a molded article in which the compressive stress is unlikely to increase when a compressive strain is applied can be easily obtained.
[0107] The flexural modulus of the resin composition constituting the foamed layer can be obtained by measurement based on JIS K7171: 2008. A test piece used for measuring the flexural modulus may be taken from a non-foamed sheet produced by heat pressing foamed beads, for example.
[0108] The resin composition constituting the foam layer preferably has a melt mass flow rate of 8 g / 10 min to 20 g / 10 min, more preferably 10 g / 10 min to 15 g / 10 min, when measured at a temperature of 230° C. and a load of 2.16 kg. In this case, the moldability of the foamed beads in a mold can be improved more easily. In addition, foamed beads capable of producing a molded article having good compressive strength can be obtained more easily by performing molding in a mold using such foamed beads. The method for measuring the melt mass flow rate of the resin composition constituting the foam layer is the same as that of the melt mass flow rate MFR of recycled polypropylene A described above, except that the foamed beads or the resin composition is used as a sample. AThe measurement method is the same as that of . More specifically, the melt mass flow rate of the resin composition constituting the foamed layer is a value measured under conditions of a test temperature of 230°C and a load of 2.16 kg based on JIS K7210-1:2014. Note that the foamed particles used as the sample may be previously subjected to a defoaming treatment.
[0109] [Bulk density of expanded particles] The bulk density of the expanded particles is 10 kg / m 3 More than 200kg / m 3 It is preferable that the thickness is less than 12 kg / m 3 More than 100kg / m 3 More preferably, it is 15 kg / m or less. 3 More than 80kg / m 3 More preferably, it is 20 kg / m or less. 3 More than 70kg / m 3 It is particularly preferable that the above-mentioned condition is satisfied. In this case, a molded product that is lightweight and has good compressive strength can be easily obtained.
[0110] The method for calculating the bulk density of expanded beads is as follows. First, the expanded beads are left to stand for 24 hours or more in an environment of 50% relative humidity, 23°C temperature, and 1 atm pressure to condition the expanded beads. The expanded beads thus obtained are filled into a measuring cylinder, and the bottom of the measuring cylinder is lightly tapped on the floor several times to stabilize the filling height of the expanded beads in the measuring cylinder. The bulk volume (unit: L) of the expanded beads is read from the graduations on the measuring cylinder. The mass (unit: g) of the expanded beads in the measuring cylinder is then divided by the aforementioned bulk volume to obtain the bulk density of the expanded beads (unit: kg / m2) by converting the value into units. 3 ) can be obtained.
[0111] [Average bubble diameter of expanded beads] The average cell diameter of the expanded beads is preferably 40 μm to 100 μm, more preferably 45 μm to 90 μm, and even more preferably 50 μm to 80 μm, in which case the moldability of the expanded beads in the mold can be further improved, and a good molded product can be easily obtained over a wide range of molding pressures.
[0112] The average bubble diameter of expanded beads is a value calculated by the following method. First, an expanded bead is cut into roughly two equal parts. Next, an enlarged photograph is taken so that the exposed cut surface is entirely within the field of view. On the enlarged photograph obtained, four line segments are drawn from the outermost surface of the expanded bead through the center to the outermost surface on the opposite side, with adjacent line segments forming equal angles (i.e., adjacent line segments forming an angle of 45°). The total length of the four line segments thus obtained is divided by the total number of bubbles intersecting the lines to determine the bubble diameter of each expanded bead.
[0113] The above procedure is carried out on 10 or more randomly selected expanded beads, and the arithmetic mean of the cell diameters obtained for each expanded bead is taken as the average cell diameter of the expanded beads.
[0114] [Closed cell ratio of expanded beads] The closed cell ratio of the expanded beads is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more, which further enhances moldability in a mold and makes it possible to easily obtain a good molded product over a wide range of molding pressures.
[0115] The closed cell ratio of the expanded beads is a value measured using an air comparison type specific gravity meter based on ASTM-D2856-70 Procedure C. The specific method for measuring the closed cell ratio of the expanded beads is as follows. Bulk volume after conditioning: about 20 cm 3The expanded particles are used as a measurement sample, and the apparent volume Va of the measurement sample is measured from the rise in the liquid level when the measurement sample is submerged in a graduated cylinder containing ethanol. After the measurement sample whose apparent volume Va has been measured is thoroughly dried, the true volume value Vx of the measurement sample is measured using an air comparison type specific gravity meter (Tokyo Science Co., Ltd.'s "Beckman Model 1000 Air Comparison Pycnometer") in accordance with procedure C described in ASTM-D2856-70. Then, using these volume values Va and Vx, the closed cell ratio (unit: %) of the measurement sample is calculated based on the following formula (1). The above operation is performed five times by changing the measurement sample, and the arithmetic average value (N=5) of the closed cell ratios of the five measurement samples is taken as the closed cell ratio (unit: %) of the expanded particles.
[0116] Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (1) In the above formula (1), the symbols have the following meanings: Vx: The true volume of the measurement sample measured by the above method, i.e., the sum of the volume of the resin constituting the foamed beads and the total volume of the air bubbles in the closed cell part in the foamed beads (unit: cm 3 ) Va: The apparent volume of the sample measured by the amount of rise in the liquid level when the sample is submerged in a graduated cylinder containing ethanol (unit: cm 3 ) W: Mass of the measurement sample (unit: g) ρ: Density of the resin that composes the foamed particles (unit: g / cm 3 )
[0117] [Ash content of expanded particles] The ash content of the expanded beads is preferably 0.1% by mass or more and 4% by mass or less, in which case the amount of components derived from post-consumer materials can be increased while ensuring good moldability of the expanded beads in a mold, making it easier to utilize post-consumer materials.
[0118] From the viewpoint of more effectively utilizing the polypropylene-based resin composition derived from post-consumer materials, the ash content of the expanded beads is more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more, while from the viewpoint of more stably realizing good in-mold moldability of the expanded beads, the ash content of the expanded beads is more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0119] In determining the preferred range of the ash content of the expanded beads, the above-mentioned upper and lower limits of the ash content of the expanded beads can be combined arbitrarily. For example, the preferred range of the ash content of the expanded beads may be 0.1% by mass or more and 3% by mass or less, 0.2% by mass or more and 3% by mass or less, or 0.5% by mass or more and 2% by mass or less.
[0120] The ash content of the expanded beads can be measured in accordance with the direct incineration method (Method A) of JIS K7250-1: 2006. More specifically, the ash content of the expanded beads can be calculated from the mass of the residue remaining after burning the expanded beads.
[0121] [High temperature peak] The expanded beads preferably have a crystal structure in which a melting peak due to melting inherent to the resin component contained in the expanded beads and one or more melting peaks located at a higher temperature than the melting peak appear in a DSC curve obtained when the expanded beads are heated from 23°C to 230°C at a heating rate of 10°C / min. Expanded beads having such a crystal structure have excellent moldability in a mold. In addition, by molding such expanded beads in a mold, a molded product having excellent compression properties can be more easily obtained. In the following, the melting peak due to melting inherent to the resin component appearing in the DSC curve is referred to as a "resin-specific peak", and the melting peak appearing at a higher temperature than the resin-specific peak is referred to as a "high-temperature peak". The resin-specific peak appears due to melting of crystals that the resin component contained in the expanded beads usually has. On the other hand, the high-temperature peak is presumed to appear due to melting of secondary crystals formed in the resin component during the manufacturing process of the expanded beads. That is, when a high-temperature peak appears in a DSC curve, it is presumed that secondary crystals are formed in the resin component.
[0122] Whether the expanded beads have the above-mentioned crystal structure or not may be determined based on a DSC curve obtained by performing differential scanning calorimetry (DSC) under the above-mentioned conditions in accordance with JIS K7122-1987. The flow rate of nitrogen gas in the measurement environment may be 30 mL per minute. In addition, 1 to 3 mg of the expanded beads may be used as a sample for DSC.
[0123] Specifically, in the DSC curve obtained when heating from 23°C to 230°C at a heating rate of 10°C / min (i.e., the first heating) as described above, both the resin peak of the resin component contained in the expanded beads and a high-temperature peak appear. In contrast, in the DSC curve obtained when the first heating is performed, the expanded beads are cooled from 230°C to 23°C at a cooling rate of 10°C / min, and then heated again from 23°C to 230°C at a heating rate of 10°C / min (i.e., the second heating), only the resin peak of the resin component contained in the expanded beads appears. Therefore, by comparing the DSC curve obtained during the first heating with the DSC curve obtained during the second heating, the resin peak and the high-temperature peak can be distinguished.
[0124] From the viewpoint of further improving the moldability and compression properties of the expanded beads, the apex temperature of the high-temperature peak of the expanded beads is preferably from 155 to 170° C., and more preferably from 160 to 170° C. From the same viewpoint, the heat of fusion of the high-temperature peak is preferably from 10 to 45 J / g, and more preferably from 12 to 35 J / g, and even more preferably from 15 to 32 J / g.
[0125] The total heat of fusion of the expanded beads is preferably 60 J / g or more and 100 J / g or less, more preferably 65 J / g or more and 90 J / g or less, and even more preferably 70 J / g or more and 85 J / g or less. In this case, the moldability of the expanded beads in a mold can be more easily improved. Furthermore, by molding such expanded beads in a mold, a molded product having excellent compression properties can be more easily obtained.
[0126] The above-mentioned high-temperature peak apex temperature, high-temperature peak heat of fusion, and total heat of fusion are values that can be obtained as follows. First, 1 to 3 mg of expanded beads are used as a sample, and a DSC curve is obtained by performing differential scanning calorimetry under conditions of heating from 23°C to 230°C at a heating rate of 10°C / min. FIG. 1 shows an example of a DSC curve. When the expanded beads have a high-temperature peak, as shown in FIG. 1, the DSC curve shows a resin-specific peak ΔH1 and a high-temperature peak ΔH2 having a peak on the higher temperature side than the peak of the resin-specific peak ΔH1. The temperature corresponding to the peak of this high-temperature peak ΔH2 is defined as the peak temperature of the high-temperature peak.
[0127] Next, a straight line L1 is drawn connecting point α corresponding to 80° C. on the DSC curve and point β corresponding to the melting end temperature T of the expanded beads. The melting end temperature T is the high temperature end point of the high temperature peak ΔH2, that is, the intersection point of the high temperature peak ΔH2 and the baseline on the higher temperature side of the high temperature peak ΔH2 on the DSC curve.
[0128] After drawing the straight line L1, a straight line L2 is drawn that passes through the maximum point γ between the resin specific peak ΔH1 and the high temperature peak ΔH2 and is parallel to the vertical axis of the graph. This straight line L2 divides the resin specific peak ΔH1 and the high temperature peak ΔH2. The heat of fusion of the high temperature peak ΔH2 can be calculated based on the area of the part of the DSC curve that constitutes the high temperature peak ΔH2 and the part surrounded by the straight lines L1 and L2. The total heat of fusion of the expanded beads can be calculated based on the area of the part of the DSC curve that constitutes the resin specific peak ΔH1, the part of the high temperature peak ΔH2, and the part surrounded by the straight line L1. That is, the total heat of fusion of the expanded beads is the sum of the heat of fusion of the resin specific peak ΔH1 and the heat of fusion of the high temperature peak ΔH2.
[0129] (Method of producing expanded polypropylene resin particles) The method for producing the expanded beads is not particularly limited, and for example, a conventional method for producing expanded polypropylene resin beads can be adopted as the method for producing the expanded beads.
[0130] The method for producing expanded beads includes an expansion step of expanding polypropylene-based resin beads to obtain expanded polypropylene-based resin beads, The resin particles have a core layer made of a polypropylene-based resin composition, The polypropylene-based resin composition constituting the core layer contains a polypropylene-based resin and a rubber-like body containing an ethylene propylene-based rubber, The rubber-like material is dispersed in a polypropylene-based resin, an amount of an acetone insoluble matter contained in an n-decane extract of the resin particles is 0.02 g or more and 0.10 g or less per 1 g of the resin particles; The melting point Tmr of the resin particles is 140° C. or more and 162° C. or less, It is preferable that the difference Tmr-Tcr between the melting point Tmr of the resin particles and the crystallization temperature Tcr of the resin particles is 38° C. or less.
[0131] [Preparation of Resin Particles] In the manufacturing method, first, resin particles having a core layer composed of the resin composition are prepared. The method of preparing the resin particles is not particularly limited. For example, when preparing resin particles having a single layer structure by the strand cut method, a resin raw material containing the polypropylene resin and the rubber-like body and additives used as necessary are fed to an extruder, and the resin raw material is heated and kneaded in the extruder to obtain a molten mixture. The molten mixture is extruded in a strand shape from a small hole in a die attached to the downstream side of the extruder. The strand-shaped extrudate is taken up and cut to a desired length to obtain resin particles.
[0132] The acetone insoluble matter contained in the n-decane extract of the resin particles (i.e., D sol -A insol The amount of D in the resin particles is preferably 0.02 g or more and 0.10 g or less per 1 g of the resin particles. sol -A insol is mainly composed of ethylene propylene rubber. D in the resin particles sol -A insolBy setting the amount of D in the resin particles within the above-mentioned specific range, the expanded beads can be obtained more easily. sol -A insol The amount of D in the resin particles is more preferably 0.03 g or more, and even more preferably 0.04 g or more, per 1 g of the resin particles. sol -A insol The amount of is more preferably 0.09 g or less, further preferably 0.08 g or less, and particularly preferably 0.07 g or less, per 1 g of resin particles.
[0133] D in resin particles sol -A insol In determining the preferred range of the amount of D sol -A insol The upper and lower limits of the amount of D in the resin particles can be arbitrarily combined. sol -A insol The preferred range of the amount of D in the resin particles may be 0.03 g or more and 0.09 g or less, 0.04 g or more and 0.08 g or less, or 0.04 g or more and 0.07 g or less, per 1 g of the resin particles. sol -A insol The method for measuring the amount of D in the expanded beads is the same as that described above, except that resin particles are used instead of expanded beads and the amount per 1 g of resin particles is calculated. sol -A insol The method for measuring the amount of is similar to that of
[0134] The melting point Tmr of the resin particles is preferably 140°C or more and 162°C or less. By setting the melting point Tmr of the resin particles within the specific range, the expanded beads can be obtained more easily. From the viewpoint of more easily improving the compression properties of the molded body, the melting point Tmr of the resin particles is preferably 143°C or more, more preferably 145°C or more, and even more preferably 146°C or more. In addition, from the viewpoint of more easily obtaining expanded beads with good moldability, the melting point Tmr of the resin particles is preferably 160°C or less, and more preferably 158°C or less.
[0135] When forming a preferred range of the melting point Tmr of the resin particles, the upper limit and the lower limit of the melting point Tmr of the resin particles described above can be combined arbitrarily. For example, the preferred range of the melting point Tmr of the resin particles may be 143°C or more and 160°C or less, 145°C or more and 158°C or less, or 146°C or more and 158°C or less. The method for measuring the melting point Tmr of the resin particles is the same as the method for measuring the melting point Tm of the expanded beads described above, except that a test piece made of resin particles is used instead of the test piece made of expanded beads.
[0136] The difference Tmr-Tcr between the melting point Tmr of the resin particles and the crystallization temperature Tcr of the resin particles is preferably 38°C or less. In this case, the expanded beads can be obtained more easily. The lower limit of the difference Tmr-Tcr in the resin particles is usually 30°C. The lower limit of the difference Tmr-Tcr is preferably 32°C. The method for measuring the crystallization temperature Tcr of the resin particles is the same as the method for measuring the crystallization temperature Tcr of the expanded beads described above, except that a test piece made of resin particles is used instead of the test piece made of expanded beads.
[0137] The resin particles preferably have a morphology in which the polypropylene resin is the matrix and the rubber body is the domain. In this case, from the viewpoint of stably increasing the moldability in the mold of the expanded beads, the average diameter of the rubber body containing the ethylene propylene rubber in the resin particles is preferably 0.1 μm or more and 2 μm or less, more preferably 0.3 μm or more and 1.5 μm or less, and even more preferably 0.5 μm or more and 1 μm or less. The method of observing the morphology of the resin particles and the method of measuring the average diameter of the rubber body are the same as the above-mentioned method of observing the morphology of the expanded beads and the method of measuring the average diameter of the rubber body, except that resin particles are used instead of the expanded beads.
[0138] The resin raw material used for producing the resin particles may be, for example, a polypropylene resin, an ethylene propylene rubber, or a polypropylene resin composition containing a rubber-like material containing an ethylene propylene rubber. When a plurality of resin components are used as the resin raw material, the operation of producing a molten mixture of these resin components and the operation of producing resin particles from the molten mixture may be carried out in the same extruder as described above. In addition, for example, the above-mentioned two operations may be carried out using separate extruders.
[0139] From the viewpoint of obtaining the expanded beads more easily, the resin composition constituting the core layer of the resin beads preferably contains a polypropylene-based resin derived from recycled polypropylene and an ethylene propylene-based rubber, i.e., the resin composition constituting the core layer preferably contains recycled polypropylene containing a polypropylene-based resin and an ethylene propylene-based rubber.
[0140] From the same viewpoint, the recycled polypropylene is preferably polypropylene A derived from post-consumer materials. The resin composition constituting the core layer of the resin particles is preferably a molten mixture of the recycled polypropylene A and polypropylene-based resin B. In this case, the melting point Tm of the recycled polypropylene A is preferably 0.01 to 0.01 mm. Ais 160°C or higher, and the melting point Tm B It is more preferable that the temperature is 130°C or higher and lower than 160°C.
[0141] [Foaming] Next, the resin particles are expanded. The method for expanding the resin particles is not particularly limited, but it is preferable to expand the resin particles by a method called a "direct expansion method" in which resin particles containing a blowing agent dispersed in an aqueous medium in a container are released together with the aqueous medium into an atmosphere with a pressure lower than that in the container. A preferred embodiment of the expansion method will be described below.
[0142] When expanding resin particles by the direct foaming method, first, the resin particles are placed in a container such as a pressure vessel and dispersed in an aqueous medium. At this time, a dispersant, a dispersion aid, a surfactant, or the like may be added as necessary to disperse the resin particles in the aqueous medium in the container.
[0143] As the dispersant, inorganic fine particles such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, etc. can be used. These inorganic fine particles may be used alone, or two or more kinds of inorganic fine particles may be used in combination. As the dispersion aid, for example, aluminum sulfate, etc. can be used. As the surfactant, for example, anionic surfactants such as sodium alkylbenzenesulfonate, sodium dodecylbenzenesulfonate, sodium alkanesulfonate, etc. can be used. These surfactants may be used alone, or two or more kinds of surfactants may be used in combination.
[0144] Next, a foaming agent is supplied into the container, and the pressure in the container is increased to impregnate the resin particles with the foaming agent. This allows resin particles containing the foaming agent to be obtained. At this time, the resin particles in the container are heated together with the aqueous medium to promote the impregnation of the foaming agent into the resin particles.
[0145] Examples of the foaming agent used in the foaming step include inorganic physical foaming agents such as carbon dioxide, air, nitrogen, helium, and argon, and organic physical foaming agents such as hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and hexane, and halogenated hydrocarbons such as ethyl chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and trans-1-chloro-3,3,3-trifluoropropene. From the viewpoint of environmental load and ease of handling, carbon dioxide is preferably used as the foaming agent. The amount of the foaming agent added is preferably 0.1 parts by mass or more and 30 parts by mass or less, and more preferably 0.5 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the resin particles.
[0146] The pressure in the container immediately before foaming is preferably 0.5 MPa (G) or more in terms of gauge pressure. On the other hand, the pressure in the container is preferably 4.0 MPa (G) or less in terms of gauge pressure. If it is within the above range, the expanded beads can be safely produced without risk of damage or explosion of the container.
[0147] After the resin particles are impregnated with the blowing agent, the contents of the container are released into an atmosphere with a lower pressure than the container, whereby the resin particles are expanded to form a cellular structure, and are cooled by the outside air (i.e., the atmosphere) to stabilize the cellular structure, thereby obtaining expanded particles.
[0148] In the above-mentioned production method, a step of adjusting the crystal structure of the resin component contained in the resin particles may be carried out between dispersing the resin particles in an aqueous medium and expanding the resin particles. By expanding the resin particles after adjusting the crystal structure of the resin component, it is possible to easily obtain expanded beads having excellent moldability in a mold and excellent compressive strength.
[0149] The method for adjusting the crystal structure of the resin component is, for example, as follows. First, a holding step is performed in which the temperature of the resin particles is held within a temperature range of (melting point of the resin composition constituting the core layer of the resin particles -15°C) or more and (melting point of the resin composition +15°C) or less for a sufficient period of time, preferably about 10 to 60 minutes. By expanding the resin particles that have been subjected to this holding step, it is possible to obtain expanded particles having a crystal structure in which the above-mentioned high-temperature peak appears in the DSC curve. The temperature inside the container during expansion is preferably (melting point of the resin composition -5°C) or more and (melting point of the resin composition +10°C) or less.
[0150] In the above-mentioned manufacturing method, the resin particles subjected to the above-mentioned holding step may be prepared in advance, and the resin particles may be expanded to obtain expanded beads. From the viewpoint of increasing the productivity of the expanded beads, it is preferable to carry out the above-mentioned holding step by heating the resin particles dispersed in the dispersion medium in a container in the presence of a foaming agent, and then release the contents of the sealed container from the container into an atmosphere with a pressure lower than the pressure in the container to expand the resin particles, thereby obtaining expanded beads having a crystal structure in which the above-mentioned high-temperature peak appears.
[0151] The reason why the mechanical strength and moldability of the expanded beads can be improved by heating and expanding under the above-mentioned conditions is thought to be that secondary crystals of the polypropylene-based resin are formed in the resin composition constituting the expanded beads, etc. Whether or not secondary crystals of the polypropylene-based resin are formed can be determined by the presence or absence of a high-temperature peak in the DSC curve.
[0152] In the above-mentioned production method, when the resin particles are expanded, the resin particles may be expanded in one stage as described above, or the resin particles may be expanded in two or more stages. When the resin particles are expanded in two stages, the resin particles are expanded by a direct expansion method or the like in the first stage expansion step to obtain first stage expanded particles. In the second stage expansion step, for example, the first stage expanded particles are pressurized with air or the like to increase the pressure (internal pressure) in the bubbles of the first stage expanded particles, and then the first stage expanded particles are heated with steam or the like to be further expanded. By expanding the resin particles in multiple stages in this way, expanded particles with a higher expansion ratio (i.e., a lower bulk density) can be easily obtained.
[0153] (Polypropylene resin foamed particle molding) After the foamed beads are filled into a mold, a heating medium such as steam is supplied into the mold to perform molding within the mold, thereby obtaining a molded product. The density of the molded product is 10 kg / m 3 More than 200kg / m 3 In this case, the molded body has a better balance between light weight and compressive strength.
[0154] From the viewpoint of increasing the compressive strength of the compact, the density of the compact is 12 kg / m 3 More preferably, it is 15 kg / m or more. 3 More preferably, it is 20 kg / m or more. 3 From the viewpoint of further increasing the lightness of the molded body, the density of the molded body is preferably 100 kg / m or more. 3 More preferably, it is 80 kg / m or less. 3 More preferably, it is 70 kg / m or less. 3 It is particularly preferable that the content is 60 kg / m or less. 3 The density of the molded article is calculated by dividing the mass (unit: g) of the molded article by the volume (unit: L) determined from the outer dimensions of the molded article, and converting the result into units.
[0155] From the viewpoint of further improving the mechanical properties of the molded article, the closed cell ratio of the molded article is preferably 70% or more, more preferably 75% or more, and even more preferably 80% or more.
[0156] The closed cell ratio of the molded body is measured in accordance with ASTM2865-70 Procedure C. Specifically, a test specimen measuring 25 mm in length, 25 mm in width, and 30 mm in height is cut out from the center of the molded body, and the geometric volume Va (unit: cm 3 ), that is, the product of the length (unit: cm), width (unit: cm), and height (unit: cm). Next, in accordance with procedure C described in ASTM-D2856-70, the true volume Vx of the test specimen is measured using an air comparison pycnometer (specifically, a Beckman Model 1000 Air Comparison Pycnometer manufactured by Tokyo Science Co., Ltd.). The true volume Vx obtained using the air comparison pycnometer is the sum (unit: cm) of the volume of the resin that constitutes the measurement sample and the total volume of the air bubbles in the closed cell portion of the measurement sample. 3 ).
[0157] The closed cell ratio (unit: %) of the test specimen is calculated by multiplying the mass W (unit: g) of the test specimen by the density ρ (unit: g / cm 3 ) and the geometric volume Va of the test specimen obtained by the above-mentioned method and the true volume Vx of the test specimen are used to express the following equation (2). Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (2)
[0158] The above procedure is carried out for five test specimens, the closed cell ratio of each test specimen is calculated, and the arithmetic mean value of the closed cell ratios of these five test specimens is regarded as the closed cell ratio of the molded article.
[0159] [Compression properties of molded body] The ratio of 5% compressive strength to 50% compressive strength of the molded body is preferably 0.50 or more, more preferably 0.52 or more, and even more preferably 0.55 or more. The energy absorption characteristics of the molded body can be evaluated based on the magnitude of compressive stress at various strain amounts. More specifically, in a stress-strain curve in which the horizontal axis represents the strain amount applied to the molded body and the vertical axis represents the compressive stress corresponding to the strain amount, the energy absorption characteristics of the molded body can be evaluated based on the magnitude of compressive stress at various strain amounts. a The closer the shape of the stress-strain curve is to a rectangle, the more desirable the energy absorption properties of the molded article. a Compressive stress σ a and strain amount ε a A strain amount ε smaller than b Compressive stress σ b The smaller the difference between the stress and strain, the closer the shape of the stress-strain curve is to a rectangle, and the smaller the strain amount ε a It can be said that the energy absorption characteristics of the molded body are good in the range up to 50% compressive strength. The upper limit of the ratio of 5% compressive strength to 50% compressive strength in the molded body is not particularly limited as long as it is within a range in which the intended object of the present invention can be achieved, but is usually 1.0, and may be 0.8 or 0.7.
[0160] Molded bodies having a compressive strength ratio within the specific range have stress-strain curves that are closer to a rectangle, and therefore have good compressive properties and can improve energy absorption characteristics over a wide range of strain amounts.
[0161] The 5% compressive strength and 50% compressive strength of the molded body are values obtained based on the method specified in JIS K7220: 2006. The method for measuring the 5% compressive strength and 50% compressive strength of the molded body will be described in more detail in the Examples. EXAMPLES
[0162] An example of the method for producing the expanded beads will now be described.
[0163] (Recycled Polypropylene A) Table 1 shows the properties of the recycled polypropylene A used in the production of the expanded beads. The polypropylene A1 used in this example was "PLC-A02" manufactured by Planic Co., Ltd., and the polypropylene A2 was "ELVBP-10" manufactured by Haison Co., Ltd. Both polypropylenes A1 and A2 are recycled polypropylenes derived from post-consumer materials and containing ethylene propylene rubber. More specifically, the main component of polypropylene A1 is polypropylene-based resin composition a1 recovered from ASR, and polypropylene A2 is polypropylene-based resin composition a recovered from parts (more specifically, bumpers) of used automobiles.
[0164] Polypropylene A1 and polypropylene A2 are cylindrical pellets, with an average length in the height direction of the pellets (average length in the extrusion direction during pellet production) of 3 mm, a diameter of the pellets of 3 mm, and an average mass of the pellets of 16 mg. Polypropylene A1 and polypropylene A2 also contain inorganic matter mainly composed of talc. When the morphology of polypropylene A1 and polypropylene A2 used in this example was observed by the method described below, both polypropylene A1 and polypropylene A2 showed a morphology in which a polypropylene resin was used as a matrix and a rubber-like body containing an ethylene propylene rubber was used as a domain.
[0165] [Table 1]
[0166] The physical properties of Polypropylene A shown in Table 1 were measured as follows.
[0167] [D in polypropylene A sol -A insol 〕 D in polypropylene A sol -A insolThat is, the amount of components soluble in n-decane and insoluble in acetone was determined by the following method. Specifically, first, about 5 g of polypropylene A was precisely weighed as a sample. The sample was added to 200 ml of n-decane and dissolved by heating at 145° C. for 30 minutes. Next, the obtained n-decane solution was cooled to 23° C. over 2 hours and left at 23° C. for 30 minutes. This caused the components insoluble in n-decane contained in the n-decane solution to precipitate. Thereafter, the n-decane solution was filtered to separate the precipitate, and an n-decane extract containing n-decane soluble components was obtained. This n-decane extract was added to acetone in an amount about three times that of the n-decane extract, and left at 23° C. for 18 hours, and the acetone insoluble components in the n-decane extract (that is, D in polypropylene A) were extracted. sol -A insol The precipitate was filtered and dried, and then the mass of the precipitate was measured. The mass (unit: g) of the precipitate thus measured was divided by the mass (unit: g) of the sample to obtain the D per 1 g of polypropylene A contained in polypropylene A. sol -A insol The amount was calculated as (unit: g).
[0168] [Morphology of Polypropylene A1] The morphology of polypropylene A1 was observed by the following method. First, a cylindrical pellet made of polypropylene A1 was cut perpendicularly to the height direction of the pellet so as to pass through the center of the pellet, and an observation sample was prepared in which the cross section of the center of the pellet was exposed. Next, the observation sample was embedded in epoxy resin and subjected to electronic staining with ruthenium tetroxide, and then a slice including the center of the pellet was prepared from the sample using an ultramicrotome or the like. The slice was placed on the grid of a transmission electron microscope (for example, "JEM-1040Flash" manufactured by JEOL Ltd.) and observed at a magnification of 5000 times, and a cross-sectional photograph of polypropylene A1 (i.e., a TEM photograph) was taken.
[0169] The morphology of the polypropylene resin phase and the rubber-like body phase containing the ethylene propylene rubber in polypropylene A1 was visually observed from the cross-sectional photograph. A cross-sectional photograph of polypropylene A1 is shown in Figure 2. In Figure 2, domain D of the rubber-like body containing the ethylene propylene rubber is shown in a relatively dark tone, and the polypropylene resin matrix M is shown in a lighter tone than domain D.
[0170] The average diameter of the rubber-like body containing the ethylene propylene-based rubber was calculated based on the TEM photograph. More specifically, the longest diameter and the shortest diameter of 50 domains randomly selected from the domains (specifically the rubber-like body) that appeared in the TEM photograph were measured. The arithmetic mean value of the longest diameter and the shortest diameter thus obtained was taken as the average diameter of the rubber-like body containing the ethylene propylene-based rubber. As a result, the average diameter of the rubber-like body containing the ethylene propylene-based rubber in the polypropylene A1 was 1.2 μm.
[0171] [Ash content] The ash content of polypropylene A was measured according to the direct ashing method (method A) of JIS K7250-1:2006. Specifically, first, about 5 g of polypropylene A was precisely weighed, and then the polypropylene A was placed in a crucible. The polypropylene A in the crucible was heated for 1 hour in an electric furnace with the atmospheric temperature set to 600°C, thereby burning the polypropylene A. After the heating was completed, the mass of the residue remaining in the crucible was measured. The ratio of the mass of the residue to the mass of the polypropylene A before heating, expressed as a percentage, was taken as the ash content of polypropylene A (unit: mass%).
[0172] [Melting point Tm A and heat of fusion H A 〕 Melting point Tm of polypropylene A Awas determined based on JIS K7121-1987. Specifically, first, the condition of a test piece made of polypropylene A was adjusted based on "(2) In the case of measuring the melting temperature after a certain heat treatment" in "3. Condition adjustment of the test piece" described in JIS K7121-1987. The test piece after the condition adjustment was heated from 23°C to 230°C at a heating rate of 10°C / min to obtain a DSC curve. The flow rate of nitrogen gas in the measurement environment was 30 mL per minute. The apex temperature of the melting peak that appeared in the DSC curve was taken as the melting point Tm A The measurement device used was a heat flux differential scanning calorimeter (manufactured by SII NanoTechnology, Inc., model number: DSC7020).
[0173] In addition, from the DSC curve obtained by performing differential scanning calorimetry in accordance with JIS K 7122-1987, the heat of fusion H A Specifically, the melting point Tm A On the DSC curve obtained in the measurement, a straight line was drawn connecting the point corresponding to 80°C on the DSC curve and the high-temperature end point of the highest melting peak. The heat of fusion H of polypropylene A was calculated based on the area surrounded by the straight line thus determined and the melting peak of the DSC curve. A was calculated.
[0174] [Melt mass flow rate MFR A 〕 According to JIS K7210-1:2014, the melt mass flow rate (MFR) of polypropylene A at a temperature of 230°C and a load of 2.16 kg A was measured.
[0175] [Flexural modulus M A 〕 Polypropylene A was heat pressed at 180°C to produce a sheet with a thickness of 4 mm, and a test piece with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm was cut out from this sheet. The flexural modulus M Awas determined in accordance with JIS K7171:2008. The radius R1 of the indenter and the radius R2 of the support table were both 5 mm, the distance between the supports was 64 mm, and the test speed was 2 mm / min.
[0176] (Polypropylene resin B) Table 2 shows the properties of the polypropylene resin B used in the production of the expanded beads. The resins B used in this example are all composed of non-recycled polypropylene resins. The resins B used in this example are either propylene-ethylene random copolymers (B1 to B4) or homopropylene (B5). In Table 2, the propylene random copolymers are indicated as "rPP" and the homopropylene as "hPP".
[0177] The methods for measuring the physical properties shown in Table 2 are the same as those for the above-mentioned polypropylene A. The "ethylene component content" of resin B in Table 2 was calculated as follows.
[0178] The content of the ethylene component in the resin B was determined by a known method determined by IR spectrum. Specifically, it was determined by the method described in Polymer Analysis Handbook (edited by the Polymer Analysis Research Forum of the Japan Analytical Chemistry Society, published in January 1995, published by Kinokuniya Shoten, page numbers and item names: 615-616 "II.2.3 2.3.4 Propylene / ethylene copolymer", 618-619 "II.2.3 2.3.5 Propylene / butene copolymer"), that is, by a method of quantitative determination based on the relationship between the value of the absorbance of ethylene and butene corrected by a predetermined coefficient and the thickness of a film-like test piece, etc.
[0179] More specifically, resin B was first heat-pressed in an environment of 180° C. to form a film, and a number of test pieces with different thicknesses of 0.1 to 0.3 mm were prepared. Next, the IR spectrum of each test piece was measured to confirm the presence of the 722 cm -1 and 733 cm -1 Absorbance at (A 722 , A 733) and 766 cm -1 Absorbance at (A 766 ) was read. Next, for each test piece, the ethylene component content (unit: mass%) in Resin B was calculated using the following formulas (3) to (5). The ethylene component contents obtained for each test piece were averaged to obtain the ethylene component content (unit: mass%) in Resin B.
[0180] (K 733 ) c =1 / 0.96{(K´ 733 ) a -0.268(K´ 722 ) a}···(3) (K 722 ) c =1 / 0.96{(K´ 722 ) a -0.150(K´ 733 ) a}···(4) Ethylene content = 0.575 {(K' 722 ) c +(K´ 733 ) c}···(5)
[0181] However, K' in formulas (3) to (5) a is the apparent absorption coefficient (K´) at each wave number. a =A / ρt) and K´ c is the corrected extinction coefficient, A is the absorbance, and ρ is the density of the resin (unit: g / cm 3 ) and t is the thickness of the film-like test piece (unit: cm).
[0182] In addition, for each test piece, the butene component content (unit: mass%) in Resin B was calculated using the following formula (6). The arithmetic average of the butene component contents obtained for each test piece was taken as the butene component content (unit: mass%) in Resin B. Butene content = 12.3 (A 766 / L) · · · (8) In the formula (8), A is the absorbance, and L is the thickness of the film-like test piece (unit: mm).
[0183] [Table 2]
[0184] Next, the configuration and manufacturing method of the expanded beads of this embodiment will be described.
[0185] Example 1 The expanded beads of Example 1 have a foamed layer made of a polypropylene-based resin composition. The resin composition constituting the foamed layer contains a polypropylene-based resin and a rubber-like body G containing an ethylene propylene-based rubber, and the rubber-like body G is dispersed in the polypropylene-based resin. In producing the expanded beads of Example 1, first, polypropylene A1, resin B1, and a bubble control agent were charged into an extruder, and a molten mixture of polypropylene A and resin B was formed in the extruder. The mass ratio of polypropylene A1 to resin B1 was set to the value shown in Table 3. In addition, zinc borate was used as the bubble control agent. The amount of zinc borate added was 0.05 mass% with respect to the total of polypropylene A1 and resin B1 (100 mass%). Thereafter, the molten mixture was extruded in a strand shape from a small hole in a die provided downstream of the extruder. The strand-shaped extrudate was taken, cooled, and then cut to an appropriate length using a pelletizer to obtain resin particles.
[0186] The resin particles thus obtained were expanded by a direct expansion method. Specifically, 1 kg of resin particles was first put into a container with an internal volume of 5 L together with 3 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.02 parts by mass of sodium alkylbenzene sulfonate as a dispersing agent, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the resin particles, and the resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0187] Then, carbon dioxide was supplied as a blowing agent into the sealed container while stirring the contents inside the container, and the temperature inside the container was raised to 155.5°C. The pressure inside the container at this time was 2.1 MPa (G). The temperature inside the container was then adjusted to 156°C, and this temperature was maintained for 15 minutes to impregnate the resin particles with the blowing agent. The container was then opened, and the contents were released into an atmospheric pressure atmosphere to expand the resin particles. As a result, the expanded beads of Example 1 were obtained.
[0188] (Examples 2 to 4) The expanded beads of Examples 2 to 4 have generally the same configuration as the expanded beads of Example 1, except that the mass ratio of polypropylene A1 and resin B1 was changed as shown in Table 3. The manufacturing method of the expanded beads in these Examples is generally the same as that of Example 1, except that the mass ratio of polypropylene A1 and resin B1 fed to the extruder was changed, and the temperature in the container during expansion was changed to 152.5°C in Example 2, 161°C in Example 3, and 158.5°C in Example 4. In Tables 3 to 7, polypropylene is abbreviated to "PP".
[0189] (Examples 5 to 7) The expanded beads of Examples 5 to 7 have generally the same configuration as the expanded beads of Example 4, except that one of polypropylene-based resins B2 to B4 was used as resin B instead of polypropylene-based resin B1 as shown in Table 4. The manufacturing method of the expanded beads in these Examples is generally the same as the manufacturing method of the expanded beads of Example 4, except that resin B supplied to the extruder was changed from polypropylene-based resin B1 to polypropylene-based resin B shown in Table 4.
[0190] Comparative Example 1 The foam layer of the expanded beads of Comparative Example 1 does not contain resin B and is composed of polypropylene A. The method for producing the expanded beads of Comparative Example 1 is generally similar to the method for producing the expanded beads of Example 1, except that, as shown in Table 5, the resin particles were produced using polypropylene A1 instead of the resin composition containing polypropylene A and resin B, and the temperature inside the container during foaming was changed to 164°C.
[0191] Comparative Example 2 The expanded beads of Comparative Example 2 have a configuration generally similar to that of Example 4, except that polypropylene-based resin B5 was used instead of polypropylene-based resin B1 as resin B, as shown in Table 5. The manufacturing method of the expanded beads in Comparative Example 2 is generally similar to that of Example 4, except that resin B supplied to the extruder was changed from polypropylene-based resin B1 to polypropylene-based resin B5, and the temperature inside the container during expansion was changed to 164°C.
[0192] Comparative Example 3 The foam layer of the expanded beads of Comparative Example 3 does not contain polypropylene A and is composed of resin B1 and resin B5, as shown in Table 5. The manufacturing method of the expanded beads of Comparative Example 3 is generally similar to the manufacturing method of the expanded beads of Example 1, except that the resin particles are produced using a resin composition composed of resin B1 and resin B5 instead of the resin composition containing polypropylene A and resin B, as shown in Table 5.
[0193] Example 8 The expanded beads of Example 8 had a bulk density of 27 kg / m3 as shown in Table 6. 3 Except for this, the expanded beads of Example 8 have a configuration generally similar to that of Example 1. The manufacturing method of the expanded beads of Example 8 is generally similar to that of Example 1, except for that the temperature in the container during expansion was changed to 155.5°C and the pressure in the container during expansion was changed to 2.8 MPa (G).
[0194] Example 9 The expanded beads of Example 9 have a configuration generally similar to that of Example 4, except that polypropylene A2 was used instead of polypropylene A1 as polypropylene A, as shown in Table 7. The production method of the expanded beads in Example 9 is generally similar to that of Example 4, except that the polypropylene A supplied to the extruder was changed from polypropylene A1 to polypropylene A2.
[0195] (Reference example 1) The foam layer of the expanded beads of Reference Example 1 does not contain polypropylene A and is composed of resin B. The method for producing the expanded beads of Reference Example 1 is generally similar to the method for producing the expanded beads of Example 1, except that the resin particles are produced using resin B1 instead of the resin composition containing polypropylene A and resin B, and the temperature inside the container during foaming is changed to 149.5°C.
[0196] (Reference example 2) The foam layer of the expanded beads of Reference Example 2 does not contain polypropylene A and is composed of resin B. The manufacturing method of the expanded beads of Reference Example 2 is generally similar to that of Reference Example 1, except that the temperature in the container during expansion was changed to 147°C and the pressure in the container was changed to 4.0 MPa (G).
[0197] Example 10 The expanded beads of Example 10 have a foamed core layer composed of a polypropylene resin composition and a fusion layer covering the foamed core layer. The polypropylene resin composition constituting the foamed core layer contains a polypropylene resin and a rubber-like body G containing an ethylene propylene rubber, and the rubber-like body G is dispersed in the polypropylene resin. In producing the expanded beads of Example 10, first, a co-extrusion device equipped with a core layer forming extruder, a fusion layer forming extruder, and a co-extrusion die connected to these two extruders is used, and the composite extruded from the co-extrusion device is cut by a strand cut method to produce multi-layered resin particles having a fusion layer.
[0198] Specifically, polypropylene A1, resin B1, a bubble control agent, and carbon black were fed to an extruder for forming a core layer, and a molten mixture for forming a core layer of polypropylene A and resin B was formed in the extruder. The blending ratio of polypropylene A1 to resin B1 in the molten mixture for forming a core layer was polypropylene A1:resin B1=15:85. Zinc borate was used as the bubble control agent. The amount of zinc borate added was 0.05% by mass relative to the total of 100% by mass of polypropylene A1 and resin B1. The amount of carbon black added was 2.8% by mass relative to the total of 100% by mass of polypropylene A1 and resin B1.
[0199] A polypropylene resin (specifically, a propylene-ethylene-butene random copolymer, melting point 122°C, melt mass flow rate 6g / 10min) and carbon black were fed to an extruder for forming a fusion layer to form a fusion layer-forming molten mixture in the extruder. The amount of carbon black added to the fusion layer-forming molten mixture was 2.8% by mass relative to 100% by mass of the polypropylene resin.
[0200] The molten mixture was merged in the die to form a composite consisting of a non-foamed cylindrical core layer and a non-foamed fusion layer covering the lateral surface of the core layer, and then co-extruded from the die in the form of a strand. The strand-shaped composite was taken, cooled, and then cut to an appropriate length using a pelletizer to obtain columnar resin particles having a core layer and a fusion layer covering the outer surface of the core layer (i.e., multi-layered resin particles). The proportion of the fusion layer in the multi-layered resin particles was 3% by mass.
[0201] Next, the multilayer resin particles were expanded by a direct expansion method. Specifically, 100 kg of the multilayer resin particles were first put into a container with an internal volume of 400 L together with 220 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.004 parts by mass of sodium alkylbenzene sulfonate as a dispersing agent, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the multilayer resin particles, and the multilayer resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0202] Then, carbon dioxide was supplied as a blowing agent into the sealed container while stirring the contents inside the container, and the temperature inside the container was raised to 158.2°C. The pressure inside the container at this time was 1.6 MPa (G). This temperature was then maintained for 15 minutes to impregnate the multilayer resin particles with the blowing agent. The container was then opened, and the contents were released under atmospheric pressure to expand the multilayer resin particles. The expanded particles thus obtained were dried for 24 hours in an atmosphere at a temperature of 23°C and a relative humidity of 50%. As a result, a first-stage expanded particle was obtained, which had an expanded core layer formed by expanding the core layer, and a non-expanded fusion layer covering the expanded core layer.
[0203] Next, the first-stage expanded beads were placed in a pressure tank as a pressure-resistant container, and the pressure tank was sealed. In this state, the pressure tank was pressurized with air as an inorganic gas, and air was impregnated into the bubbles of the first-stage expanded beads so that the pressure in the bubbles of the first-stage expanded beads was 0.35 MPa (G). After the application of internal pressure to the first-stage expanded beads was completed, the first-stage expanded beads were removed from the pressure tank and placed in a metal drum. Then, steam was supplied to the first-stage expanded beads and they were heated under atmospheric pressure. As a result, the first-stage expanded beads were further expanded to obtain expanded beads (i.e., second-stage expanded beads). As a result, the expanded beads of Example 10 were obtained. The proportion of the fusion layer in the expanded beads was 3 mass%.
[0204] Example 11 The expanded beads of Example 11 have a foamed core layer composed of a polypropylene resin composition and a fusion layer covering the foamed core layer. The polypropylene resin composition constituting the foamed core layer contains a polypropylene resin and a rubber-like body G containing an ethylene propylene rubber, and the rubber-like body G is dispersed in the polypropylene resin. The expanded beads of Example 11 are cylindrical expanded beads having a through hole penetrating the inside in the axial direction. In producing the expanded beads of Example 11, first, a co-extrusion device equipped with a core layer forming extruder, a fusion layer forming extruder, and a co-extrusion die connected to these two extruders was used, and the composite extruded from the co-extrusion device was cut by a strand cut method to produce multi-layered resin particles having a fusion layer. The co-extrusion die used in Example 11 is equipped with a mechanism capable of forming a through hole in the core layer of the multi-layered resin particle.
[0205] Specifically, polypropylene A1, resin B1, a bubble control agent, and carbon black were fed to an extruder for forming a core layer, and a molten mixture for forming a core layer of polypropylene A and resin B was formed in the extruder. The mass ratio of polypropylene A1 to resin B1 in the molten mixture for forming a core layer was polypropylene A1:resin B1=17:83. Zinc borate was used as the bubble control agent. The amount of zinc borate added was 0.05% by mass relative to the total of 100% by mass of polypropylene A1 and resin B1. The amount of carbon black added was 2.8% by mass relative to the total of 100% by mass of polypropylene A1 and resin B1.
[0206] A polypropylene resin (specifically, a propylene-ethylene random copolymer, melting point 133°C, melt mass flow rate 24g / 10min) and carbon black were fed to an extruder for forming a fusion layer to form a molten mixture for forming a fusion layer in the extruder. The amount of carbon black added to the molten mixture for forming a fusion layer was 2.8% by mass relative to 100% by mass of the polypropylene resin.
[0207] The molten mixture was merged in the die to form a composite consisting of a non-foamed cylindrical core layer and a non-foamed fusion layer covering the lateral surface of the core layer, and then co-extruded from the die in the form of a strand. The strand-shaped composite was taken, cooled, and cut to an appropriate length using a pelletizer to obtain cylindrical multilayer resin particles having a core layer with a through hole passing through the inside in the axial direction and a fusion layer covering the outer surface of the core layer. The proportion of the fusion layer in the multilayer resin particles was 5% by mass.
[0208] Next, the multilayer resin particles were expanded by a direct expansion method. Specifically, 100 kg of the multilayer resin particles were first put into a container with an internal volume of 400 L together with 220 L of water as an aqueous medium. Next, 0.3 parts by mass of a dispersant, 0.004 parts by mass of sodium alkylbenzene sulfonate as a dispersing agent, and 0.01 parts by mass of aluminum sulfate were added to the container relative to 100 parts by mass of the multilayer resin particles, and the multilayer resin particles were dispersed in the aqueous medium. Kaolin was used as the dispersant.
[0209] Then, carbon dioxide was supplied as a blowing agent into the sealed container while stirring the inside of the container, and the temperature inside the container was raised to 159.3°C. The pressure inside the container at this time was 1.5MPa (G). This temperature was maintained for 15 minutes to impregnate the multilayer resin particles with the blowing agent. Then, the container was opened and the contents were released under atmospheric pressure to expand the multilayer resin particles. The expanded particles thus obtained were dried for 24 hours in an atmosphere at a temperature of 23°C and a relative humidity of 50%. As a result, a cylindrical one-stage expanded particle was obtained, which had a foamed core layer, a foamed core layer having through holes, and a non-foamed fusion layer covering the foamed core layer.
[0210] Next, the first-stage expanded particles were placed in a pressure tank as a pressure-resistant container, and the pressure tank was sealed. In this state, the pressure tank was pressurized with air as an inorganic gas, and the air bubbles were impregnated with air so that the pressure in the bubbles of the first-stage expanded particles was 0.35 MPa (G). After the application of internal pressure to the first-stage expanded particles was completed, the first-stage expanded particles were taken out of the pressure tank and placed in a metal drum. Then, steam was supplied to the first-stage expanded particles and heated under atmospheric pressure. As a result, the first-stage expanded particles were further expanded to obtain expanded particles (i.e., second-stage expanded particles). As a result, the expanded particles of Example 11 were obtained. The proportion of the fusion layer in the expanded particles was 5 mass%. The expanded particles had through holes penetrating the inside in the axial direction, the average hole diameter of the through holes was 0.69 mm, and the ratio of the average hole diameter of the through holes to the average outer diameter of the expanded particles was 0.20.
[0211] The average diameter of the through holes was determined as follows. First, 100 expanded beads were randomly selected, and these expanded beads were cut at the position where the cross-sectional area was maximum along a plane perpendicular to the axial direction to expose the cut surface of the expanded beads. Next, a photograph of the cut surface of the expanded beads was taken, and the cross-sectional area of the through holes in the cut surface (i.e., the opening area) was measured by performing image analysis. Then, the diameter of a virtual perfect circle having the same area as the cross-sectional area of the through holes was calculated, and this value was taken as the diameter of the through holes in each expanded bead. The above operation was performed for 100 expanded beads, and the arithmetic average value of the obtained diameters of the through holes was taken as the average diameter of the through holes in the expanded beads.
[0212] The average outer diameter of the expanded beads was determined as follows. First, 100 expanded beads were randomly selected, and these expanded beads were cut at the position where the cross-sectional area was maximum along a plane perpendicular to the axial direction to expose the cut surface of the expanded beads. Next, a photograph of the cut surface of the expanded beads was taken, and the cross-sectional area of the expanded beads including the through holes (i.e., the area of the region surrounded by the outer peripheral edge of the expanded beads on the cut surface) was measured by performing image analysis. Then, the diameter of a virtual perfect circle having the same area as the cross-sectional area of the expanded beads was calculated, and this value was taken as the outer diameter of each expanded bead. The above operation was performed for 100 expanded beads, and the arithmetic average value of the obtained outer diameters of the expanded beads was taken as the average outer diameter of the expanded beads.
[0213] Tables 3 to 7 show various properties of the resin particles, expanded beads, and molded articles obtained by molding the expanded beads in a mold of Examples 1 to 9 and Comparative Examples 1 to 3 obtained above.
[0214] The bulk density of the expanded beads of Example 10 was 27 kg / m 3 and D in the foam particles sol -A insol The amount of was 0.03 g per 1 g of expanded beads, the melting point Tm was 148°C, the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc was 35°C, and the heat of fusion of the high-temperature peak was 20 J / g. The moldable range of the expanded beads of Example 10 was 0.27-0.31 MPa(G). The density of the molded product of Example 10 was 30 kg / m 3 The 5% compressive strength was 220 kPa, the 50% compressive strength was 420 kPa, and the compressive strength ratio was 0.52.
[0215] The bulk density of the expanded beads of Example 11 is 33 kg / m 3 and D in the foam particles sol -A insol The amount of was 0.03 g per 1 g of expanded beads, the melting point Tm was 148°C, the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc was 35°C, and the heat of fusion of the high-temperature peak was 22 J / g. The moldable range of the expanded beads of Example 11 was 0.30-0.34 MPa(G). The density of the molded product of Example 11 was 35 kg / m 3The 5% compressive strength was 140 kPa, the 50% compressive strength was 270 kPa, and the compressive strength ratio was 0.52.
[0216] The expanded beads of Reference Example 1 did not contain a rubber-like material containing an ethylene propylene-based rubber. The bulk density of the expanded beads of Reference Example 1 was 45 kg / m 3 The average cell diameter was 110 μm, the closed cell ratio was 96%, the melting point Tm was 143° C., the difference Tm−Tc was 40° C., the ash content was 0 mass%, the melt mass-flow rate was 9 g / 10 min, the flexural modulus was 950 MPa, the apex temperature Th of the high-temperature peak was 156° C., and the heat of fusion of the high-temperature peak was 16 J / g. The moldable range of the expanded beads of Reference Example 1 was 0.28-0.32 MPa (G). The density of the molded body of Reference Example 1 was 50 kg / m 3 The closed cell ratio was 86%, the 5% compressive strength was 210 kPa, the 50% compressive strength was 425 kPa, and the compressive strength ratio was 0.49.
[0217] The expanded beads of Reference Example 2 did not contain a rubber-like material containing an ethylene propylene-based rubber. The bulk density of the expanded beads of Reference Example 2 was 27 kg / m 3 The average cell diameter was 150 μm, the closed cell ratio was 96%, the melting point Tm was 143° C., the difference Tm−Tc was 40° C., the ash content was 0 mass%, the melt mass-flow rate was 9 g / 10 min, the flexural modulus was 950 MPa, the apex temperature Th of the high-temperature peak was 156° C., and the heat of fusion of the high-temperature peak was 16 J / g. The moldable range of the expanded beads of Reference Example 2 was 0.28-0.32 MPa (G). The density of the molded body of Reference Example 2 was 30 kg / m 3 The closed cell ratio was 85%, the 5% compressive strength was 95 kPa, the 50% compressive strength was 240 kPa, and the compressive strength ratio was 0.40.
[0218] [Melting point Tm of expanded particles and melting point Tmr of resin particles] The melting point Tm of the expanded particles and the melting point Tmr of the resin particles were measured by the same method as described above for polypropylene A, except that expanded particles or resin particles were used instead of polypropylene A. A The measurement method is the same as that of
[0219] [Crystallization temperature Tc of expanded beads and crystallization temperature Tcr of resin beads] Based on JIS K7121-1987, the crystallization temperature Tc of the expanded beads was measured using a heat flux differential scanning calorimeter. More specifically, the expanded beads were first heated from 23°C to 230°C at a heating rate of 10°C / min, and then the temperature of 230°C was maintained for 10 minutes. Then, the expanded beads were cooled from 230°C to 30°C at a cooling rate of 10°C / min to obtain a DSC curve. The flow rate of nitrogen gas in the measurement environment was 30mL per minute. The apex temperature of the crystallization peak in this DSC curve was taken as the crystallization temperature Tc of the expanded beads. When multiple crystallization peaks appear in the DSC curve, the apex temperature of the crystallization peak with the highest peak height was taken as the crystallization temperature Tc of the expanded beads.
[0220] The method for measuring the crystallization temperature Tcr of the resin particles is the same as the method for measuring the crystallization temperature Tc of the expanded beads described above, except that resin particles are used instead of the expanded beads.
[0221] [Bulk density of expanded particles] The expanded beads were left to stand for 24 hours or more in an environment of 50% relative humidity, 23°C temperature, and 1 atm pressure to adjust the state of the expanded beads. 3 The expanded particles were filled into a measuring cylinder, and the bottom of the measuring cylinder was lightly tapped on the floor several times to stabilize the filling height of the expanded particles in the measuring cylinder. The exact bulk volume (unit: L) of the expanded particles was then read from the graduations on the measuring cylinder. The mass (unit: g) of the expanded particles in the measuring cylinder was then divided by the aforementioned bulk volume and converted into units to obtain the bulk density of the expanded particles (unit: kg / m 3 ) was calculated.
[0222] [Average bubble diameter of expanded beads] The expanded beads were cut into roughly two equal parts. Next, an enlarged photograph was taken so that the exposed cut surface was entirely within the field of view. Four line segments were drawn on the enlarged photograph from the outermost surface of the expanded beads through the center to the outermost surface on the opposite side, with the adjacent line segments forming equal angles (i.e., the angle between adjacent line segments was 45°). The total length of the four line segments thus obtained was divided by the total number of bubbles intersecting the lines to determine the bubble diameter of each expanded bead.
[0223] The above procedure was carried out on 10 or more randomly selected expanded beads, and the arithmetic mean of the cell diameters obtained for each expanded bead was taken as the average cell diameter of the expanded beads.
[0224] [Closed cell ratio of expanded beads] The closed cell ratio of the foamed beads was measured using an air comparison type specific gravity meter according to ASTM-D2856-70 procedure C. Specifically, first, the bulk volume after conditioning was about 20 cm 3 The expanded particles were used as a measurement sample, and the measurement sample was submerged in a graduated cylinder containing ethanol. The apparent volume Va of the measurement sample was measured from the amount of rise in the liquid level at this time. After the measurement sample whose apparent volume Va was measured was thoroughly dried, the true volume value Vx of the measurement sample was measured using an air comparison type specific gravity meter (Tokyo Science Co., Ltd.'s "Beckman Model 1000 Air Comparison Pycnometer") in accordance with procedure C described in ASTM-D2856-70. Then, using these volume values Va and Vx, the closed cell ratio (unit: %) of the measurement sample was calculated based on the following formula (1). The above operation was performed five times by changing the measurement sample, and the arithmetic average value (N = 5) of the closed cell ratios of the five measurement samples was taken as the closed cell ratio (unit: %) of the expanded particles.
[0225] Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (1)
[0226] In the above formula (1), the symbols have the following meanings: Vx: The true volume of the measurement sample measured by the above method, i.e., the sum of the volume of the resin constituting the foamed beads and the total volume of the air bubbles in the closed cell part in the foamed beads (unit: cm 3 ) Va: The apparent volume of the sample measured by the amount of rise in the liquid level when the sample is submerged in a graduated cylinder containing ethanol (unit: cm 3 ) W: Mass of the measurement sample (unit: g) ρ: Density of the resin that composes the foamed particles (unit: g / cm 3 )
[0227] [D in the foam particles sol -A insol and D in the resin particles sol -A insol 〕 D in foam particles sol -A insol That is, the amount of components soluble in n-decane and insoluble in acetone was determined by the following method. Specifically, first, about 5 g of expanded particles was precisely weighed as a sample. The sample was added to 200 ml of n-decane and heated to 145° C. for 30 minutes for dissolution. Next, the obtained n-decane solution was cooled to 23° C. over 2 hours and left at 23° C. for 30 minutes. This caused the components insoluble in n-decane in the n-decane solution to precipitate. Thereafter, the n-decane solution was filtered to separate the precipitate, and an n-decane extract containing n-decane soluble components was obtained. This n-decane extract was added to acetone in an amount about three times that of the n-decane extract, and left at 23° C. for 18 hours, and the acetone insoluble components in the n-decane extract (i.e., D in the expanded particles) were analyzed. sol -A insol The precipitate was filtered and dried, and then the mass of the precipitate was measured. The mass of the precipitate (unit: g) thus measured was divided by the mass of the sample (unit: g) to obtain the D per 1 g of expanded beads. sol -A insol The amount (unit: g) was calculated.
[0228] In addition, D in the resin particles sol -A insolThe method for measuring the amount of D in the expanded beads was the same as that described above, except that resin particles were used instead of expanded beads and the amount was calculated per 1 g of resin particles. sol -A insol The method for measuring the amount of is similar to that of
[0229] [Morphology of Expanded Beads and Morphology of Resin Beads] The morphology of the expanded beads was observed by the following method. First, the expanded beads were cut through the center to prepare a sample for observation in which the cross section of the center of the expanded beads was exposed. Next, the sample for observation was embedded in epoxy resin and subjected to electronic staining with ruthenium tetroxide, and then a slice including the center of the expanded beads was prepared from the sample using an ultramicrotome or the like. The slice was placed on the grid of a transmission electron microscope ("JEM-1040Flash" manufactured by JEOL Ltd.) and observed at a magnification of 5000 times, and a cross-sectional photograph of the expanded beads (i.e., a TEM photograph) was taken.
[0230] From the cross-sectional photograph, the morphology of the polypropylene resin phase and the rubber-like body phase containing the ethylene propylene rubber in the foamed layer was visually observed. As an example, FIG. 3 shows a cross-sectional photograph of the foamed beads of Example 4. As shown in FIG. 3, it was confirmed that the foamed beads 11 of the foamed beads 1 have a morphology in which the domain D of the rubber-like body G containing the ethylene propylene rubber is dispersed in the matrix M of the polypropylene resin. Based on the cross-sectional photograph obtained in this way, the average diameter of the rubber-like body in the morphology of the foamed beads was calculated by the same method as the method for calculating the average diameter of the rubber-like body in the morphology of the polypropylene A.
[0231] The method for observing the morphology of the resin particles is the same as the method for observing the morphology of the expanded particles described above, except that resin particles are used instead of expanded particles. As an example, FIG. 4 shows a cross-sectional photograph of the resin particles of Example 4. As shown in FIG. 4, it was confirmed that the resin particles 10 have a morphology in which the domain D of the rubber-like body G containing the ethylene propylene-based rubber is dispersed in the matrix M of the polypropylene-based resin. In addition, based on the cross-sectional photograph obtained in this way, the average diameter of the rubber-like body in the morphology of the resin particles was calculated by the same method as the method for calculating the average diameter of the rubber-like body in the morphology of polypropylene A.
[0232] [Ash content of resin particles and expanded particles] The method for measuring the ash content of the resin particles and the ash content of the expanded beads is the same as the method for measuring the ash content of polypropylene A described above, except that resin particles or expanded beads are used instead of polypropylene A.
[0233] [Melt mass flow rate of resin composition constituting expanded beads] The expanded beads were defoamed by heat pressing at a temperature of 180°C for 3 minutes, and a sheet composed of the resin composition constituting the expanded beads was produced. The sheet was cut to obtain pellet-shaped samples, and the melt mass-flow rate was measured at a temperature of 230°C and a load of 2.16 kg in accordance with JIS K7210-1:2014.
[0234] [Flexural modulus of resin composition constituting expanded beads] The foamed beads were heat pressed at 180°C to produce a sheet with a thickness of 4 mm, and a test piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm was cut out from this sheet. The flexural modulus of this test piece was determined in accordance with JIS K7171:2008. The radius R1 of the indenter and the radius R2 of the support table were both 5 mm, the distance between the supports was 64 mm, and the test speed was 2 mm / min.
[0235] [Resin specific peak and high temperature peak] The apex temperature and heat of fusion of the high-temperature peak were obtained from a DSC curve obtained by performing differential scanning calorimetry (DSC) in accordance with JIS K7122-1987. Specifically, first, about 3 mg of expanded particles was used as a sample, and the sample was heated from 23°C to 230°C at a heating rate of 10°C / min to perform differential scanning calorimetry to obtain a DSC curve. The flow rate of nitrogen gas in the measurement environment was 30 mL per minute. Based on this DSC curve, the apex temperature T l and the apex temperature T of the high-temperature peak ΔH2 h The difference in peak temperatures T h -T l The " column shows the apex temperature T of the high-temperature peak ΔH2. h From the resin specific peak ΔH1 apex temperature T l The values shown are those after subtracting .
[0236] Next, a straight line L1 was drawn connecting point α corresponding to 80°C on the DSC curve and point β corresponding to the end temperature of melting T of the expanded beads. Furthermore, a straight line L2 was drawn parallel to the vertical axis of the graph, passing through the maximum point γ existing between the resin intrinsic peak ΔH1 and the high-temperature peak ΔH2, and the resin intrinsic peak ΔH1 and the high-temperature peak ΔH2 were divided by the straight line L2.
[0237] The heat of fusion of the resin-specific peak ΔH1 was calculated based on the area of the portion of the DSC curve that constitutes the resin-specific peak ΔH1 and the portion surrounded by the straight lines L1 and L2. The heat of fusion of the high-temperature peak ΔH2 was calculated based on the area of the portion of the DSC curve that constitutes the high-temperature peak ΔH2 and the portion surrounded by the straight lines L1 and L2.
[0238] The above procedure was performed three times using different samples, and the arithmetic mean value of the heat of fusion of the resin-specific peak ΔH1 obtained in each measurement was taken as the heat of fusion of the resin-specific peak ΔH1 of the expanded beads, and the arithmetic mean value of the heat of fusion of the high-temperature peak ΔH2 was taken as the heat of fusion of the high-temperature peak ΔH2 of the expanded beads.
[0239] [Density of Molded Body] Molding was performed in the mold at the lowest molding pressure within the above-mentioned moldable range to obtain an expanded bead molding. The mass (unit: g) of this expanded bead molding was divided by the volume (unit: L) calculated from the outer dimensions of the molding, and the density (unit: kg / m) of the molding was calculated by converting the unit. 3 ) was calculated.
[0240] [Moldable range] In evaluating the moldable range, molded bodies were produced by in-mold molding while changing the molding pressure during main heating from 0.26 MPa (G) to 0.42 MPa (G) in increments of 0.01 MPa, and the lower molding pressure limit and moldable range were determined based on the surface properties, fusion properties, and recovery properties of the obtained molded bodies.
[0241] The manufacturing method of the molded body is as follows. First, the foamed particles are placed in a pressure vessel, and the pressure vessel is pressurized with air to impregnate the foamed particles with air, and an internal pressure of 0.10 MPa (G) is applied to the foamed particles. Next, the foamed particles to which the internal pressure is applied are filled into a mold by a cracking filling method. In this example, a mold having a cavity capable of molding a flat molded body having a length of 250 mm, a width of 200 mm, and a thickness of 50 mm is used. In the cracking filling, the foamed particles are filled into the mold with a cracking gap of 5 mm (i.e., a cracking amount of 10%) opened in the thickness direction of the molded body, and then the mold is completely closed to mechanically compress the foamed particles in the mold.
[0242] Next, steam was supplied into the mold to perform in-mold molding. In the in-mold molding, first, steam was supplied into the mold for 5 seconds with the drain valve of the mold open to perform preheating. Next, the drain valve was closed, and steam was supplied from one side of the mold until a pressure 0.08 MPa (G) lower than the molding pressure during main heating was reached, to perform a first one-sided heating. Next, steam was supplied from the other side of the mold until a pressure 0.04 MPa (G) lower than the molding pressure during main heating was reached, to perform a second one-sided heating. After that, steam was supplied from both sides of the mold until the molding pressure during main heating was reached, to perform main heating. After main heating was completed, the pressure in the mold was released, and the molded body was cooled in the mold until the surface pressure due to the foaming force of the molded body became 0.04 MPa (G).
[0243] Thereafter, the molded body removed from the mold was left in an oven at 80°C for 12 hours to undergo a curing process. After the curing process, the molded body was left at rest for 24 hours under conditions of 50% relative humidity, 23°C, and 1 atm to condition the molded body. The surface properties, fusion properties, and recovery properties of the molded body after condition adjustment were evaluated, and the range of molding pressures that passed all items in the evaluation criteria described below (i.e., molding pressures at which a passing product could be obtained) was determined as the moldable range. The wider the moldable range, the better the moldability. In addition, the lower the moldable molding pressure, the more likely it is that molding in the mold can be performed with a smaller amount of steam, and therefore the better the productivity.
[0244] The methods for evaluating the surface property, fusion property and recovery property in the evaluation of the moldable range are as follows.
[0245] ·Superficiality A 100 mm x 100 mm square was drawn in the center of one of the skin surfaces in the thickness direction of the molded body, and then a diagonal was drawn from one of the corners of the square. The number of voids on the diagonal, that is, the number of voids having a size of 1 mm x 1 mm or more among the gaps formed between the foamed particles, was then counted. If the number of voids was two or less, it was judged as passing, and if it was three or more, it was judged as failing.
[0246] - Weldability The molded body was broken into roughly equal parts in the longitudinal direction. 100 or more randomly selected expanded beads exposed on the fracture surface were visually observed to determine whether the expanded beads were broken inside the beads (i.e., expanded beads with material destruction) or at the interface between the expanded beads. The ratio of the number of expanded beads that were broken inside the beads to the total number of expanded beads observed was calculated as a percentage (i.e., material destruction rate), and this value was taken as the fusion rate. A fusion rate of 80% or more was judged to be acceptable, and a fusion rate of less than 80% was judged to be unacceptable.
[0247] ·Recovery In a plan view of the molded body from the thickness direction, the thickness of the molded body was measured at four positions 10 mm inward from each vertex of the surface bounded by the 250 mm vertical side and the 200 mm horizontal side toward the center of the surface, and at the center of the surface. Next, the ratio (unit: %) of the thickness of the thinnest part to the thickness of the thickest part among the measured parts was calculated. If the thickness ratio thus obtained was 95% or more, it was judged to be passed, and if it was less than 95%, it was judged to be failed.
[0248] [Closed cell ratio of molded body] Molding was performed in the mold at the lowest molding pressure within the above-mentioned moldable range to obtain a molded body. A test piece measuring 25 mm in length × 25 mm in width × 30 mm in height was cut out from the center of this molded body, and the geometric volume Va (unit: cm 3 ), that is, the product of the vertical dimension (unit: cm), horizontal dimension (unit: cm), and height dimension (unit: cm), was calculated. Next, in accordance with procedure C described in ASTM-D2856-70, the true volume value Vx of the test specimen was measured using an air comparison pycnometer (specifically, a "Beckman Model 1000 Air Comparison Pycnometer" manufactured by Tokyo Science Co., Ltd.). The true volume value Vx obtained using the air comparison pycnometer is the sum (unit: cm) of the volume of the resin constituting the measurement sample and the total volume of the air bubbles in the closed cell portion of the measurement sample. 3 ).
[0249] The mass W (unit: g) of the specimen obtained above and the density ρ (unit: g / cm 3 ) and the geometric volume Va and true volume Vx of the test specimen obtained by the above-mentioned method were used to calculate the closed cell ratio (unit: %) of the test specimen according to the following formula (2). Closed cell ratio = (Vx-W / ρ)×100 / (Va-W / ρ) (2)
[0250] The above procedure was carried out for five test specimens, the closed cell ratio of each test specimen was calculated, and the arithmetic mean value of the closed cell ratios of these five test specimens was regarded as the closed cell ratio of the molded article.
[0251] [5% and 50% compressive strength of molded body] Molding was performed in the mold at the lowest molding pressure within the moldable range described above, to obtain a molded body. A rectangular parallelepiped test piece measuring 50 mm in length, 50 mm in width, and 25 mm in thickness was taken from the center of this molded body. A compression test was performed on the test piece at a compression speed of 10 mm / min based on the method specified in JIS K7220:2006, and a stress-strain curve was obtained. The compression test was performed in a laboratory at 23°C. The 5% deformation compressive stress and 50% deformation compressive stress of the test piece were calculated based on this stress-strain curve, and these values were used as the 5% compression strength and 50% compression strength of the molded body. The "50% compression strength / density" column in Tables 3 to 7 lists the value obtained by dividing the 50% compression strength value by the density of the molded body (unit: kPa / (kg / m 3 ) is recorded in the "Compressive strength ratio" column, and the ratio of 5% compressive strength to 50% compressive strength, that is, the value obtained by dividing 5% compressive strength by 50% compressive strength, is recorded in the "Compressive strength ratio" column.
[0252] [Table 3]
[0253] [Table 4]
[0254] [Table 5]
[0255] [Table 6]
[0256] [Table 7]
[0257] As shown in Tables 3 and 4, the polypropylene resin composition constituting the foamed layer in the foamed beads of Examples 1 to 7 contains a polypropylene resin and a rubber-like material containing an ethylene propylene rubber, and the rubber-like material is dispersed in the polypropylene resin. sol -A insol The amount of , the melting point Tm, and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc are all within the above-mentioned specific ranges. Therefore, the expanded beads of Examples 1 to 7 have good moldability in a mold and can form a molded product with a low rate of increase in compressive stress with an increase in compressive strain.
[0258] On the other hand, as shown in Table 5, the expanded beads of Comparative Example 1 had a D sol -A insol The amount of is too large. In addition, the melting point Tm and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc of the expanded beads of Comparative Example 1 are both outside the above-mentioned specific range. Therefore, the expanded beads of Comparative Example 1 could not form a good molded product.
[0259] The melting point Tm and the difference Tm-Tc between the melting point Tm and the crystallization temperature Tc of the expanded beads of Comparative Example 2 are both outside the above-mentioned specific ranges, and therefore the expanded beads of Comparative Example 2 could not form a good molded product.
[0260] The expanded beads of Comparative Example 3 do not contain a rubber-like material containing an ethylene propylene rubber. Therefore, the compression strength ratio of the molded body made of the expanded beads of Comparative Example 3 is lower than that of the molded body made of the expanded beads of the Examples, and the rate of increase in compression stress with an increase in compression strain is high. In addition, the expanded beads of Comparative Example 3 had a narrower range of molding pressure at which a good molded body could be obtained than the expanded beads of the Examples.
[0261] Furthermore, from a comparison between Examples 1 to 7 and Reference Example 1, and a comparison between Example 8 and Reference Example 2, it can be seen that expanded beads containing a rubber-like material including an ethylene propylene-based rubber can reduce the rate of increase in compressive stress associated with an increase in the compressive strain of the molded body, compared to expanded beads not containing a rubber-like material.
[0262] Furthermore, as shown in Table 7, it can be seen that such effects are also obtained in the expanded beads of Example 9, which are derived from automotive parts and contain recycled polypropylene A containing ethylene propylene-based rubber in the resin composition.
[0263] Moreover, as shown in Examples 10 and 11, it can be understood that such effects can also be obtained with expanded beads having a fusion layer or expanded beads having through holes.
[0264] The above describes specific embodiments of the expanded beads and molded articles of the present invention based on the examples. However, the specific embodiments of the expanded beads and molded articles made from these expanded beads of the present invention are not limited to those in the examples, and the configurations can be changed as appropriate within the scope of the invention without deviating from the spirit of the invention. [Explanation of symbols]
[0265] 1. Polypropylene resin foam particles G Rubber-like body
Claims
1. A polypropylene-based resin foamed particle having a foamed layer made of a polypropylene-based resin composition, the polypropylene-based resin composition constituting the foamed layer contains a polypropylene-based resin and a rubber-like body containing an ethylene propylene-based rubber, The rubber-like material is dispersed in a polypropylene-based resin, an amount of an acetone insoluble matter contained in an n-decane extract of the expanded beads is 0.02 g or more and 0.10 g or less per 1 g of the expanded beads; The melting point Tm of the expanded beads is 140° C. or more and 162° C. or less, The expanded polypropylene resin beads have a difference (Tm-Tc) between the melting point (Tm) of the expanded beads and the crystallization temperature (Tc) of the expanded beads of 38° C. or less.
2. 2. The expanded polypropylene resin particles according to claim 1, wherein the average diameter of the rubber-like bodies is 0.1 μm or more and 2 μm or less.
3. 2. The polypropylene-based resin expanded particles according to claim 1, wherein the polypropylene-based resin composition constituting the foamed layer contains a polypropylene-based resin derived from recycled polypropylene and an ethylene propylene-based rubber.
4. 2. The polypropylene resin expanded particles according to claim 1, wherein the polypropylene resin composition constituting the foamed layer has a flexural modulus of 800 MPa or more and 1,300 MPa or less.
5. 5. A polypropylene resin foamed bead molding obtained by molding the polypropylene resin foamed bead according to claim 1 in a mold.
Citation Information
Patent Citations
Method for producing polypropylene-based resin pre-foamed particle
JP2013155386A